Method for synthesizing chabazite including organic and inorganic structure directing agents and chabazite-type zeolite having a flake-like morphology
The synthesis of chabazite-type zeolites with controlled aluminum distribution and morphology using mixed structure-directing agents addresses the challenges of SCR catalysts, enhancing catalytic performance and stability for NOx reduction.
Patent Information
- Application Number
- JP2022533250
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2020-07-31
- Publication Date
- 2025-11-13
- Estimated Expiration
- 2040-07-31
AI Technical Summary
Current SCR catalysts face challenges in maintaining high catalytic activity under hydrothermal conditions and varying engine exhaust temperatures, particularly in managing NOx emissions with tailored adsorption and catalytic functionality, while being cost-effective and efficient.
A method for synthesizing chabazite-type zeolites with controlled aluminum distribution using a mixture of organic and inorganic structure-directing agents, specifically incorporating potassium cations, to achieve tailored catalytic and adsorption properties, including the formation of intergrowth phases and flake-like morphology.
The method results in zeolites with improved catalytic performance for NOx reduction, offering enhanced stability and efficiency under varying temperature conditions, while reducing production costs through optimized aluminum distribution and morphology control.
Smart Images

Figure 0007769450000012 
Figure 0007769450000013 
Figure 0007769450000014
Abstract
Description
[Technical Field]
[0001] The present disclosure relates to methods for the preparation of CHA-type zeolites, catalyst compositions containing such zeolites, and catalyst articles and systems that use such catalyst compositions. [Background technology]
[0002] Various treatment methods have been used to treat NOx-containing gas mixtures to reduce air pollution. One treatment type involves catalytic reduction of nitrogen oxides. There are two processes: (1) non-selective reduction processes, in which carbon monoxide, hydrogen, or hydrocarbons are used as reducing agents, and (2) selective reduction processes, in which ammonia or an ammonia precursor is used as a reducing agent. In selective reduction processes, high levels of nitrogen oxide removal can be achieved using small amounts of reducing agent, resulting in the formation of primarily nitrogen and steam according to the following equation: 4NO + 4NH3 + O2 → 4N2 + 6H2O (standard SCR reaction) 2NO2 + 4NH3 → 3N2 + 6H2O (slow SCR reaction) NO + NO2 + 2NH3 → 2N2 + 3H2O (high-speed SCR reaction)
[0003] Catalysts used in SCR processes ideally should be able to maintain good catalytic activity under hydrothermal conditions over a wide operating temperature range, e.g., from 200°C to over 600°C. SCR catalysts are commonly used under hydrothermal conditions, such as during the regeneration of soot filters, a component of exhaust gas treatment systems used to remove particulates.
[0004] Current catalysts used in SCR processes include molecular sieves, such as zeolites, that have been ion-exchanged with catalytic metals, such as iron or copper. Zeolites are crystalline materials with fairly uniform pore sizes ranging from about 3 to about 10 angstroms in diameter, depending on the type of zeolite and the type and amount of cations contained in the zeolite. Zeolites with eight-membered ring pore openings and double six-ring secondary structural units, particularly zeolites with cage-like structures, are particularly suitable for use as SCR catalysts. Metal-promoted zeolite catalysts, including iron- and copper-promoted zeolite catalysts, are known for the selective catalytic reduction of nitrogen oxides with ammonia.
[0005] When metal-exchanged (e.g., copper-exchanged), NO is produced by NH3. x One exemplary zeolite that has been shown to be an effective catalyst for the selective catalytic reduction of benzene is a zeolite with a chabazite (CHA) framework. CHA-type zeolites are small-pore zeolites with 8-membered ring pore openings (approximately 3.8 angstroms) accessible through three-dimensional porosity. The cage-like structure results from double 6-ring structural units connected by 4 rings. Zeolites with the CHA structure can be prepared, for example, according to the methods disclosed in U.S. Pat. Nos. 4,544,538 and 6,709,644, which are incorporated herein by reference.
[0006] The catalytic properties of zeolites are defined not only by their framework connectivity but also by the microscopic atomic arrangement of framework aluminum (Al) atoms that generates catalytically active sites. In the case of CHA-type zeolites, which are highly symmetric frameworks composed of a single unique tetrahedral site (T-site), distinct arrangements of framework Al atoms are defined as isolated (x ≥ 3) or paired (x = 1, 2) configurations in six-membered rings (6-MR), the latter being related to the divalent Co 2+ and Cu 2+These different framework Al assemblages in CHA have been quantified by cation exchange. These different framework Al assemblages in CHA affect the turnover rate for methanol dehydration to dimethyl ether, the time-on-stream stability for methanol-to-olefin catalysis, the CO adsorption equilibrium constant, and the partial methane oxidation (PMO) to methanol and NO with NH. x This has been linked to differences in speciation of extra-framework cationic Cu and Fe complexes that mediate the selective catalytic reduction (SCR) of urea (Chen, H.-Y., “Urea-SCR Technology for Denox after Treatment of Diesel Exhausts”; Nova, I., Tronconi, E., Eds.; Springer New York: New York, NY, 2014, pp. 123-147).
[0007] Zeolite materials, with their well-defined crystalline frameworks, provide a convenient framework for tailored materials design efforts, facilitating the coupling of data and insights from experimental and theoretical evaluations of catalytic structure and function. Synthetic protocols that intentionally influence the placement of substituted heteroatoms in the zeolite framework, and theoretical models of structure-directing agent (SDA)-framework interactions that can aid in the development of such protocols, will provide a means to prepare zeolites with tailored catalytic and adsorption properties. Cationic SDA molecules interact with the framework SiO during zeolite crystallization. 4 / 2 The tetrahedral units are anionic AlO 4 / 2 - It has been suggested that this facilitates substitution of tetrahedral units and influences the location of Al at specific T-site positions based on the proximity of charged moieties of SDA and anionic lattice Al sites. + )), inorganic cations (e.g., Cu 2+Considering a single type of extraframework cation—either cations or protons—in the CHA framework, first-principles density functional theory (DFT) and molecular dynamics (MD) simulations to model the interactions between these cations and Al sites have provided evidence for the dominant role of electrostatic interactions on the stability of various framework Al arrangements. However, the effect of mixtures of cationic organic and inorganic SDAs on the energetics of framework Al arrangements is less well understood. Crystallization of high-silica (Si / Al > 7) zeolites typically relies on the presence of organic SDA molecules to balance the charge of anionic lattices through electrostatic interactions and stabilize the silica-containing portions of the zeolite lattice through dispersive interactions, which can be tailored to selectively direct crystallization into desired crystalline phases. The incorporation of alkali cations during zeolite crystallization can be used to control the crystal morphology of MFI, spatially bias Al incorporation in FAU, and also influence the arrangement of Al sites in MFI-type zeolites between voids of various sizes (straight and sinusoidal channels and their intersections) and between separated and paired configurations.
[0008] Already, SDA contains primarily isolated Al sites, presumably allowing the occupation of each CHA cage (diameter ∼0.7 nm) by only one TMAda. + As a result of the adamantyl groups (diameter approximately 0.7 nm) that impose steric constraints to confine the molecules (Zones, SI, Journal of the Chemical Society, Faraday Transactions 1991, 87, 3709-3716), CHA-type zeolites (Si / Al = 15) are suitable for the low charge density organic TMAda + It has been reported that TMAda crystallizes from a synthesis medium containing only CHA (Di Iorio, JR; Gounder, R. Chem. Mater. 2016, 28, 2236-2247). While keeping all other synthesis variables constant, TMAda crystallizes from a synthesis medium containing only CHA (Di Iorio, JR; Gounder, R. Chem. Mater. 2016, 28, 2236-2247). + Na + Partially replacing with (0 <Na + / TMAda +<2), 1 TMAda per CHA cage + Contains molecules but saturated Co 2+ Na corrected for the total number of paired Al sites determined by ion exchange level + CHA-type zeolites (Si / Al = 15) containing various amounts of Na have been crystallized (Di Iorio, JR; Gounder, R. Chem. Mater. 2016, 28, 2236-2247; Di Iorio et al., ACS Catal. 2017, 7, 6663-6674). + / TMAda + Above 2, a phase transition to MOR occurs, possibly reflecting a preference for forming denser frameworks to satisfy the electrostatic constraints imposed by the charge density of the synthesis medium (Di Iorio, JR; Gounder, R. Chem. Mater. 2016, 28, 2236-2247; Blackwell et al., Angewandte Chemie International Edition 2003, 42, 1737-1740; Lewis et al., Studies in Surface Science and Catalysis 2004, 154, 364-372; Park et al., Chemistry of Materials 2014, 26, 6684-6694). + / TMAda + The preparation of CHA-type zeolites using inclusion synthesis gels is further disclosed in U.S. Patent Application Publication No. 2017 / 0107114, the disclosure of which is incorporated herein by reference in its entirety.
[0009] Increasingly stringent emissions regulations require NOx to be produced while exhibiting sufficient high temperature thermal stability, especially under lean and low engine exhaust temperature conditions. xThere is an increasing need to develop SCR catalysts with improved ability to manage emissions. There is a need for zeolite materials with tailored adsorption and catalytic functionality, and methods for making small pore zeolites, such as CHA, that are efficient and low cost, but also provide materials with properties suitable for SCR catalysis. In particular, there is a need in the art for methods for removing NO from exhaust gas streams. x There is a continuing need for effective SCR catalysts to efficiently and effectively mitigate emissions. The Al distribution in zeolites is related to structural stability, deactivation, and coking in acid catalysis for hydrocarbons and alcohols, so engineering this distribution can benefit these technologies. The distribution of aluminum in zeolites can be influenced by the amount of extra-framework metal ions (e.g., Cu) that can be exchanged on the zeolite. 2+ , (CuOH) + ) and the structure of these ions, which are responsible for the NO x Because Al is a catalytic site in the selective catalytic reduction of Al, manipulating this distribution can provide benefits to these technologies. Thus, there is a significant unmet need in the art for a synthetic procedure to directly and systematically control the Al distribution in chabazite-type zeolites at a fixed Si / Al ratio by manipulating only the type and amount of structure-directing agent used.
[0010] Chabazite, an example of a zeolite with a CHA framework, is typically found in a limited range of morphologies, such as cubic, truncated cubic, spherical / ellipsoidal, and worm-like crystals. See, for example, Kumar et al., J. Am. Chem. Soc. 137 (2015), 13007-13017; Bohstrom et al., Microporous and Mesoporous Materials 195 (2014), 294-302; and Guo et al., Chemical Engineering Journal 358 (2019), 331-339, each of which is incorporated herein by reference in its entirety. Certain morphologies may exhibit different behaviors, for example, during substrate coating or under catalytic conditions, each of which may prove advantageous in terms of catalytic performance (e.g., SCR performance). Therefore, synthetic protocols that intentionally influence the morphology of zeolites can provide a means for preparing catalytic materials with tailored catalytic properties and improved performance. Summary of the Invention
[0011] The present disclosure generally provides methods for producing chabazite-type zeolites.
[0012] In some embodiments, methods are provided for producing chabazite-type zeolites with controlled aluminum distribution. For purposes of this disclosure, a zeolite structure with controlled aluminum distribution is one in which the placement and arrangement (i.e., distribution) of aluminum atoms in its framework is controlled by the preparation method. The combined experimental and theoretical approaches disclosed herein reveal different interactions between mixtures of organic and inorganic structure-directing agents (SDAs) used in the crystallization of CHA-type zeolites, providing a framework for designing zeolites with tailored adsorption and catalytic functions. Surprisingly, according to this disclosure, the use of mixtures of organic and inorganic cations with different charge densities as SDAs during zeolite crystallization results in the formation of anionic framework Al centers (Al-O(-Si-O)).x -Al) can be influenced between isolated (x≧3) and paired (x=1, 2) sequences. + and TMAda + The CHA-type zeolite crystallized from the mixture of K + The cation is transferred from the CHA cage to the TMAda + The results showed that the substitution of Na leads to the formation of mainly isolated Al sites within the same composition range. + (Na + / TMAda + <2) than K + (K + / TMAda + Crystallization can be achieved from synthesis media containing inorganic to organic SDA ratios that are over an order of magnitude higher than those of CHA-type zeolites (<50), which has a favorable impact on cost. Finally, in accordance with the present disclosure, it has surprisingly been found that organic and inorganic cations cooperate or compete for occupancy within the pores of CHA-type zeolites, resulting in some embodiments in intergrowths of crystalline phases (mixed domains).
[0013] Thus, in one aspect, the present disclosure provides a method for synthesizing a zeolite having a CHA crystalline framework, the method comprising preparing a mixture of water, an aluminum source, a silica source, a source of organic structure directing agent, and an inorganic structure directing agent to form a synthesis gel, where the inorganic structure directing agent is a source of potassium cations, and subjecting the synthesis gel to a crystallization process to crystallize chabazite-type zeolite.
[0014] In some embodiments, the source of potassium cations is potassium hydroxide.
[0015] In some embodiments, the preparation comprises a first mixing step comprising adding a source of organic structure directing agent, a source of inorganic structure directing agent, and a source of aluminum to water to form an aluminum-containing aqueous solution and mixing the aqueous solution for a first period of time, and a second mixing step comprising adding a source of silicon to the aluminum-containing aqueous solution and mixing for a second period of time to form an aluminosilicate-containing solution.
[0016] In some embodiments, the first and second periods of time are each independently from about 1 second to about 24 hours.
[0017] In some embodiments, the first and second mixing steps are carried out at a temperature of from about 20°C to about 100°C.
[0018] In some embodiments, the crystallization process involves mixing the synthesis gel at a temperature of about 140° C. to about 200° C. for a time period of about 24 hours to about 6 days.
[0019] In some embodiments, the method further comprises filtering the crystals formed during the heating step.
[0020] In some embodiments, the source of the organic structure directing agent is N,N,N-trimethyl-1-adamantylammonium hydroxide (TMAda).
[0021] In some embodiments, the amount of TMAda and the amount of potassium cation source are such that the molar ratio of potassium cations to N,N,N-trimethyl-1-adamantylammonium cations is in the range of about 1 to about 20.
[0022] In some embodiments, the source of aluminum is aluminum hydroxide, aluminum nitrate, aluminosilicate, aluminum chloride, aluminum phosphate, or aluminum isopropoxide. In some embodiments, the source of aluminum is aluminum hydroxide or aluminum isopropoxide. In some embodiments, the source of aluminum is aluminum hydroxide.
[0023] In some embodiments, the source of silicon is colloidal silica, a silicon alkoxide compound, fumed silica, amorphous silica, or an aluminosilicate. In some embodiments, the source of silicon is colloidal silica.
[0024] In some embodiments, the OH / Si ratio of the synthesis gel is from about 0.1 to about 0.5.
[0025] In some embodiments, the CHA-type zeolite has a controlled aluminum distribution, the controlled aluminum distribution comprising an arrangement of anionic framework Al centers according to the formula (Al-O(-Si-O)x-Al), where x=1 or 2 and the anionic framework Al centers are in a paired arrangement, or where x≧3 and the anionic framework Al centers are in a separated arrangement.
[0026] In some embodiments, the silica-to-alumina ratio (SAR) of the synthesis gel is selected to provide a CHA-type zeolite having an SAR of from about 2 to about 60. In some embodiments, the silica-to-alumina ratio (SAR) of the synthesis gel is selected to provide a CHA-type zeolite having an SAR of from about 6 to about 20.
[0027] In some embodiments, the ratio of silicon source to aluminum source to TMAda to potassium cation source to water is represented by 1 SiO2 / 0.033 Al2O3 / X TMAdaOH / 0.5*(0.5-X)K2O / 44 H2O, where the value of X is between 0.01 and 0.25.
[0028] In some embodiments, the zeolite CHA crystalline framework of the disclosed method is an intergrowth zeolite comprising a first CHA phase and a second CHA phase.
[0029] In some embodiments, the intergrowth zeolite has a crystal size of about 0.1 μm to about 15 μm.
[0030] In some embodiments, the intergrowth zeolite comprises a first CHA phase and a second CHA phase, wherein the first CHA phase and the second CHA phase each independently have a diameter of about 2338 Å. 3 ~2489Å 3 and the unit cell volume of the first CHA phase is different from the unit cell volume of the second CHA phase. In some embodiments, the unit cell volumes of the first CHA phase and the second CHA phase are 2353 Å or less. 3 ~2411Å 3 The range is.
[0031] In some embodiments, the first CHA phase and the second CHA phase each independently have a silica-to-alumina ratio (SAR) of from about 4 to about 100, and the SAR of the first CHA phase is different from the SAR of the second CHA phase.
[0032] In some embodiments, the first CHA phase has a higher SAR than the second CHA phase. In some embodiments, the SAR of the first CHA phase is about 10 to about 40, and the SAR of the second CHA phase is about 6 to about 8. In some embodiments, the SAR of the first CHA phase is about 10 to about 20. In some embodiments, the SAR of the first CHA phase is about 10 to about 15.
[0033] In some embodiments, the first CHA phase represents about 5% to about 95% of the intergrowth zeolite, the first CHA phase having a potassium cation to aluminum ratio greater than 0.5, and the second CHA phase having a potassium cation to aluminum ratio less than about 0.5.
[0034] In some embodiments, the first CHA phase, the second CHA phase, or both comprise a silicoaluminophosphate (SAPO) composition. In some embodiments, the SAPO composition is SAPO-34 or SAPO-44.
[0035] In another aspect, an intergrowth zeolite having a chabazite (CHA) crystalline framework is provided, the CHA crystalline framework comprising a first CHA phase and a second CHA phase, the first CHA phase and the second CHA phase each independently having a diameter of about 2338 Å. 3 ~2489Å 3 and the unit cell volume of the first CHA phase is different from the unit cell volume of the second CHA phase. In some embodiments, the unit cell volumes of the first CHA phase and the second CHA phase are 2353 Å or less. 3 ~2411Å 3 The range is.
[0036] In some embodiments, the first CHA phase and the second CHA phase each independently have a silica-to-alumina ratio (SAR) of from about 4 to about 100, and the SAR of the first CHA phase is different from the SAR of the second CHA phase.
[0037] In some embodiments, the first CHA phase has a higher SAR than the second CHA phase. In some embodiments, the SAR of the first CHA phase is about 10 to about 40, and the SAR of the second CHA phase is about 6 to about 8. In some embodiments, the SAR of the first CHA phase is about 10 to about 20. In some embodiments, the SAR of the first CHA phase is about 10 to about 15.
[0038] In some embodiments, the first CHA phase represents about 5% to about 95% of the intergrowth zeolite, the first CHA phase having a potassium cation to aluminum ratio greater than 0.5, and the second CHA phase having a potassium cation to aluminum ratio less than about 0.5.
[0039] In some embodiments, the first CHA phase, the second CHA phase, or both comprise a silicoaluminophosphate (SAPO) composition. In some embodiments, the SAPO composition is SAPO-34 or SAPO-44.
[0040] In some embodiments, the fraction of aluminum atoms at crystal lattice framework sites of the CHA-type zeolite framework in the isolated configuration ranges from about 0.90 to about 1.00, and in some embodiments, the fraction of aluminum atoms at crystal lattice framework sites of the CHA-type zeolite framework in the isolated configuration ranges from about 0.95 to about 1.00.
[0041] In another aspect, nitrogen oxides (NO x A selective catalytic reduction (SCR) catalyst effective for the mitigation of CO₂ is provided, the SCR catalyst comprising the zeolitic material disclosed herein promoted with a promoter metal.
[0042] In some embodiments, the promoter metal is present in an amount of about 1.0 wt. % to about 10 wt. %, calculated as metal oxide, based on the total weight of the SCR catalyst. In some embodiments, the promoter metal is present in an amount of about 4 to about 6 wt. %. In some embodiments, the promoter metal is selected from iron, copper, and combinations thereof.
[0043] In another aspect, an SCR catalyst article effective for reducing nitrogen oxides (NOx) from engine exhaust gas is provided, the SCR catalyst article including a substrate having a selective catalytic reduction (SCR) catalyst disclosed herein disposed on at least a portion thereof.
[0044] In some embodiments, the substrate is a honeycomb substrate. In some embodiments, the honeycomb substrate is a flow-through substrate or a wall-flow filter.
[0045] In another aspect, an exhaust gas treatment system is provided that includes an engine producing an exhaust gas stream, wherein an SCR catalyst article disclosed herein is positioned downstream of the engine and in fluid communication with the exhaust gas stream.
[0046] In another aspect, nitrogen oxides (NO x ) is effective in reducing low-temperature NO x An adsorption (LT-NA) catalyst is provided, which comprises the intergrowth zeolite material disclosed herein promoted with a platinum group metal.
[0047] In another aspect, a catalyst composition effective for one or more conversions selected from olefin formation, hydrocarbon cracking, removal of alcohols to form olefins, formation of methylamines from methanol and ammonia, and partial oxidation of methane to methanol is provided, the catalyst composition comprising an intergrowth zeolite material disclosed herein.
[0048] In some embodiments, a method for producing chabazite-type zeolite having a predominantly flake-like morphology is provided. Surprisingly, it has been discovered that the use of a synthesis gel composition having a high ratio of potassium ions to organic structure directing agent (OSDA) enables the synthesis of CHA-type zeolite having a predominantly flake-like morphology.
[0049] In a further aspect, the present disclosure provides a zeolitic material having a CHA crystalline framework, wherein the crystals of the zeolitic material have a predominantly flaky morphology as determined by scanning electron microscopy (SEM) energy dispersive X-ray spectroscopy (SEM / EDS). In some embodiments, at least about 40% of the crystals have a flaky morphology as determined by SEM / EDS. In some embodiments, at least about 70% by weight of the crystals have a flaky morphology.
[0050] In some embodiments, the average length and width of the crystals is about 0.3 to about 1.5 μm, and the average thickness is less than about 0.050 μm, hi some embodiments, the average thickness is less than about 0.025 μm.
[0051] In some embodiments, the aspect ratio of the crystals is greater than about 20. In some embodiments, the aspect ratio of the crystals is from about 20 to about 40.
[0052] In some embodiments, the zeolitic material has a silica to alumina molar ratio (SAR) of from about 2 to about 60. In some embodiments, the SAR is from about 10 to about 30.
[0053] In some embodiments, the zeolitic material has a silica to potassium molar ratio of less than about 20. In some embodiments, the silica to potassium molar ratio is from about 12 to about 17.
[0054] In another aspect, a method is provided for synthesizing a zeolitic material having a CHA crystalline framework and a predominantly flaked morphology, the method comprising: preparing a mixture of water, an aluminum source, a silicon source, an organic structure directing agent, and an inorganic structure directing agent to form a synthesis gel, wherein the inorganic structure directing agent comprises potassium cations; and subjecting the synthesis gel to a crystallization process to crystallize the zeolitic material.
[0055] In some embodiments, the preparation includes a first mixing step comprising adding an organic structure directing agent, an inorganic structure directing agent, and an aluminum source to water to form an aluminum-containing aqueous solution and mixing the aqueous solution for a first period of time, and a second mixing step comprising adding a silicon source to the aluminum-containing aqueous solution and mixing for a second period of time to form an aluminosilicate-containing solution. In some embodiments, the first and second periods of time are each independently from about 1 second to about 24 hours. In some embodiments, the first and second mixing steps are carried out at a temperature of from about 20°C to about 100°C.
[0056] In some embodiments, the crystallization process involves mixing the synthesis gel for a time period of about 12 hours to about 6 days at a temperature of about 100°C to about 200°C. In some embodiments, the temperature is about 160°C to about 180°C.
[0057] In some embodiments, the method further comprises filtering the crystals formed during the heating step.
[0058] In some embodiments, the organic structure directing agent is selected from the group consisting of N,N,N-trimethyl-1-adamantylammonium hydroxide (TMAdaOH), trimethylcyclohexylammonium hydroxide, tetraethylammonium hydroxide, benzyltrimethylammonium hydroxide, 1,1,3,5-tetramethylpiperidinium hydroxide, choline hydroxide, N,N-dimethylpiperidinium hydroxide, trimethyl-2-ammonium exo-norbornane, and N-methyl-3-quinuclidinol. In some embodiments, the organic structure directing agent is TMAdaOH.
[0059] In some embodiments, the inorganic structure directing agent is potassium hydroxide. In some embodiments, the amount of TMAdaOH and the amount of potassium cations present in the synthesis gel are such that the molar ratio of potassium cations to TMAdaOH is about 10 or greater. In some embodiments, the molar ratio of potassium cations to TMAdaOH is about 15 to about 50. In some embodiments, the amount of TMAdaOH and the amount of silicon source present in the synthesis gel are such that the molar ratio of TMAdaOH to silicon atoms is less than about 0.05. In some embodiments, the molar ratio of TMAdaOH to silicon atoms is about 0.05 to about 0.01.
[0060] In some embodiments, the source of aluminum is a zeolite, aluminum isopropoxide, or aluminum hydroxide. In some embodiments, the source of aluminum is aluminum hydroxide.
[0061] In some embodiments, the source of silicon is colloidal silica, silicon alkoxide, fumed silica, amorphous silica, or an aluminosilicate. In some embodiments, the source of silicon is colloidal silica.
[0062] In some embodiments, the silica-to-alumina ratio (SAR) of the synthesis gel is selected to provide a zeolitic material having an SAR of from about 2 to about 60. In some embodiments, the silica-to-alumina ratio (SAR) of the synthesis gel is selected to provide a zeolitic material having an SAR of from about 10 to about 30.
[0063] In yet a further aspect, there is provided a zeolitic material having a CHA crystalline framework and a predominantly flake-like morphology as determined by scanning electron microscopy / energy dispersive X-ray spectroscopy (SEM / EDS), prepared by the methods disclosed herein.
[0064] In yet another aspect, nitrogen oxides (NO x A selective catalytic reduction (SCR) catalyst effective for the mitigation of CO₂ is provided, the SCR catalyst comprising the zeolitic material disclosed herein promoted with a promoter metal.
[0065] In some embodiments, the promoter metal is present in an amount of about 1.0 wt. % to about 10 wt. % calculated as promoter metal oxide, based on the total weight of the SCR catalyst. In some embodiments, the promoter metal is present in an amount of about 4 to about 6 wt. %. In some embodiments, the promoter metal is a transition metal. In some embodiments, the promoter metal is selected from iron, copper, manganese, and combinations thereof. In some embodiments, the promoter metal is selected from iron, copper, and combinations thereof.
[0066] The present invention includes, but is not limited to, the following embodiments.
[0067] Embodiment 1: A method of synthesizing a zeolite having a CHA crystalline framework, the method comprising: preparing a mixture of water, an aluminum source, a silica source, a source of organic structure directing agent, and an inorganic structure directing agent to form a synthesis gel, wherein the inorganic structure directing agent is a source of potassium cations; and subjecting the synthesis gel to a crystallization process to crystallize the zeolite having a CHA crystalline framework.
[0068] Embodiment 2: The method of embodiment 1, wherein the source of potassium cations is potassium hydroxide.
[0069] Embodiment 3: The method of embodiment 1 or 2, wherein preparing comprises a first mixing step comprising adding a source of organic structure directing agent, a source of inorganic structure directing agent, and a source of aluminum to water to form an aluminum-containing aqueous solution and mixing the aqueous solution for a first period of time; and a second mixing step comprising adding a source of silicon to the aluminum-containing aqueous solution and mixing for a second period of time to form an aluminosilicate-containing solution.
[0070] Embodiment 4: The method of any one of embodiments 1 to 3, wherein the first and second periods are each independently from about 1 second to about 24 hours.
[0071] Embodiment 5: The method of any one of embodiments 1 to 4, wherein the first and second mixing steps are carried out at a temperature of about 20°C to about 100°C.
[0072] Embodiment 6: The method of any one of embodiments 1 to 5, wherein the crystallization process comprises mixing the synthesis gel at a temperature of about 140°C to about 200°C for a time period of about 24 hours to about 6 days.
[0073] Embodiment 7: The method of any one of embodiments 1-6, further comprising filtering the crystals formed during the heating step.
[0074] Embodiment 8: The method of any one of embodiments 1-7, wherein the source of organic structure directing agent is N,N,N-trimethyl-1-adamantylammonium hydroxide (TMAda).
[0075] Embodiment 9: The method of any one of embodiments 1 to 8, wherein the amount of TMAda and the amount of potassium cation source are such that the molar ratio of potassium cations to N,N,N-trimethyl-1-adamantylammonium cations is in a molar ratio ranging from about 1 to about 20.
[0076] Embodiment 10: The method of any one of embodiments 1-9, wherein the source of aluminum is aluminum hydroxide, aluminum nitrate, aluminosilicate, aluminum chloride, aluminum phosphate, or aluminum triisopropoxide.
[0077] Embodiment 11: The method of any one of embodiments 1-10, wherein the source of aluminum is aluminum hydroxide or aluminum triisopropoxide.
[0078] Embodiment 12: The method of any one of embodiments 1 to 11, wherein the source of aluminum is aluminum hydroxide.
[0079] Embodiment 13: The method of any one of embodiments 1-12, wherein the source of silicon is colloidal silica, a silicon alkoxide compound, fumed silica, amorphous silica, or an aluminosilicate.
[0080] Embodiment 14: The method of any one of embodiments 1 to 13, wherein the source of silicon is colloidal silica.
[0081] Embodiment 15: The method of any one of embodiments 1 to 14, wherein the OH / Si ratio of the synthesis gel is from about 0.1 to about 0.5.
[0082] Embodiment 16: A CHA-type zeolite having a controlled aluminum distribution, the controlled aluminum distribution being represented by the formula (Al-O(-Si-O) x 16. The method of any one of the preceding claims, comprising an arrangement of anionic framework Al centers according to the formula: (x -Al), where x=1 or 2 and the anionic framework Al centers are in a paired arrangement, or x≧3 and the anionic framework Al centers are in an isolated arrangement.
[0083] Embodiment 17: The method of any one of embodiments 1 to 16, wherein the silica-to-alumina ratio (SAR) of the synthesis gel is selected to provide a CHA-type zeolite having an SAR of from about 2 to about 60.
[0084] Embodiment 18: The method of any one of embodiments 1 to 17, wherein the silica-to-alumina ratio (SAR) of the synthesis gel is selected to provide a CHA-type zeolite having an SAR of from about 6 to about 20.
[0085] Embodiment 19: The method of any one of embodiments 1 to 18, wherein the ratio of the silicon source to the aluminum source to the TMAda to the potassium cation source to water is represented by the formula: 1 SiO2 / 0.033 Al2O3 / X TMAdaOH / 0.5*(0.5-X)K2O / 44 H2O, where the value of X is 0.01 to 0.25.
[0086] Embodiment 20: The zeolite having a CHA crystalline framework is an intergrowth zeolite comprising a first CHA phase and a second CHA phase, wherein the first CHA phase and the second CHA phase each independently have a diameter of about 2338 Å. 3 ~2489Å 3 20. The method of any one of embodiments 1-19, wherein the unit cell volume of the first CHA phase is different from the unit cell volume of the second CHA phase.
[0087] Embodiment 21: The method of any one of embodiments 1-20, wherein the first CHA phase and the second CHA phase each independently have a silica-to-alumina ratio (SAR) of from about 4 to about 100, and the SAR of the first CHA phase is different from the SAR of the second CHA phase.
[0088] Embodiment 22: The method of any one of embodiments 1 to 21, wherein the first CHA phase has a higher SAR than the second CHA phase.
[0089] Embodiment 23: The method of any one of embodiments 1 to 22, wherein the first CHA phase has an SAR of about 10 to about 40 and the second CHA phase has an SAR of about 6 to about 8.
[0090] Embodiment 24: The method of any one of embodiments 1 to 23, wherein the SAR of the first CHA phase is from about 10 to about 20.
[0091] Embodiment 25: The method of any one of embodiments 1 to 24, wherein the SAR of the first CHA phase is from about 10 to about 15.
[0092] Embodiment 26: The method of any one of embodiments 1 to 25, wherein the first CHA phase represents from about 5% to about 95% of the intergrowth zeolite, the first CHA phase having a potassium cation to aluminum ratio greater than 0.5, and the second CHA phase having a potassium cation to aluminum ratio less than about 0.5.
[0093] Embodiment 27: The method of any one of embodiments 1-26, wherein the first CHA phase, the second CHA phase, or both, comprises a silicoaluminophosphate (SAPO) composition.
[0094] Embodiment 28: The method of any one of embodiments 1 to 27, wherein the SAPO composition is SAPO-34 or SAPO-44.
[0095] Embodiment 29: The method of any one of embodiments 1 to 28, wherein the intergrowth zeolite crystal size is from about 0.1 to about 15 μm.
[0096] Embodiment 30: An intergrowth zeolite having a CHA crystalline framework, the CHA crystalline framework comprising a first CHA phase and a second CHA phase, the first CHA phase and the second CHA phase each independently having a diameter of about 2338 Å. 3 ~2489Å 3 and the unit cell volume of the first CHA phase is different from the unit cell volume of the second CHA phase.
[0097] Embodiment 31: The intergrowth zeolite of embodiment 30, wherein the first CHA phase and the second CHA phase each independently have a silica-to-alumina ratio (SAR) of from about 4 to about 100, and the SAR of the first CHA phase is different from the SAR of the second CHA phase.
[0098] Embodiment 32: The intergrowth zeolite of embodiment 30 or 31, wherein the first CHA phase has a higher SAR than the second CHA phase.
[0099] Embodiment 33: The intergrowth zeolite of any one of embodiments 30 to 32, wherein the first CHA phase has an SAR of about 10 to about 40 and the second CHA phase has an SAR of about 6 to about 8.
[0100] Embodiment 34: The intergrowth zeolite of any one of embodiments 30 to 33, wherein the first CHA phase has an SAR of from about 10 to about 20.
[0101] Embodiment 35: The intergrowth zeolite of any one of embodiments 30 to 34, wherein the SAR of the first CHA phase is from about 10 to about 15.
[0102] Embodiment 36: The intergrown zeolite of any one of embodiments 30 to 35, wherein the first CHA phase represents from about 5% to about 95% of the intergrown zeolite, the first CHA phase having a potassium cation to aluminum ratio greater than 0.5, and the second CHA phase having a potassium cation to aluminum ratio less than about 0.5.
[0103] Embodiment 37: The intergrowth zeolite of any one of embodiments 30-36, wherein the first CHA phase, the second CHA phase, or both, comprise a silicoaluminophosphate (SAPO) composition.
[0104] Embodiment 38: The intergrown zeolite of any one of embodiments 30 to 37, wherein the SAPO composition is SAPO-34 or SAPO-44.
[0105] Embodiment 39: The intergrown zeolite of any one of embodiments 30 to 38, wherein the intergrown zeolite crystal size is from about 0.1 to about 15 μm.
[0106] Embodiment 40: The intergrowth zeolite of any one of embodiments 30-39, wherein the fraction of aluminum atoms at crystal lattice framework positions of the CHA crystalline framework in the isolated configuration ranges from about 0.90 to about 1.00.
[0107] Embodiment 41: The intergrowth zeolite of any one of embodiments 30-40, wherein the fraction of aluminum atoms at crystal lattice framework positions of the CHA crystalline framework in the isolated configuration ranges from about 0.95 to about 1.00.
[0108] Embodiment 42: A selective catalytic reduction (SCR) catalyst effective for abating nitrogen oxides (NOx) in an exhaust gas stream, the SCR catalyst comprising the intergrown zeolite material of any one of embodiments 30-41 promoted with a promoter metal.
[0109] Embodiment 43: The SCR catalyst of embodiment 42, wherein the promoter metal is present in an amount of about 1.0 wt. % to about 10 wt. %, calculated as metal oxide, based on the total weight of the SCR catalyst.
[0110] Embodiment 44: The SCR catalyst of embodiment 42 or 43, wherein the promoter metal is present in an amount of about 4 to about 6 weight percent.
[0111] Embodiment 45: The SCR catalyst of any one of embodiments 42-44, wherein the promoter metal is selected from iron, copper, and combinations thereof.
[0112] Embodiment 46: Nitrogen oxides (NO x 46. An SCR catalyst article effective for mitigating a selective catalytic reduction (SCR) catalyst comprising a substrate having the SCR catalyst of any one of embodiments 42-45 disposed on at least a portion of the substrate.
[0113] Embodiment 47: The SCR catalyst article of embodiment 46, wherein the substrate is a honeycomb substrate.
[0114] Embodiment 48: The SCR catalyst article of embodiment 47, wherein the honeycomb substrate is a flow-through substrate or a wall-flow filter.
[0115] Embodiment 49: An exhaust gas treatment system comprising: an engine generating an exhaust gas stream; and the SCR catalyst article of any one of embodiments 46-48 positioned downstream from the engine and in fluid communication with the exhaust gas stream.
[0116] Embodiment 50: Nitrogen oxides (NO x 42. A low temperature NOx adsorption (LT-NA) catalyst effective for the abatement of NOx adsorption, the LT-NA catalyst comprising an intergrown zeolite material according to any one of embodiments 30 to 41 promoted with a platinum group metal. x Adsorption (LT-NA) catalyst.
[0117] Embodiment 51: A catalyst composition effective for one or more conversions selected from olefin formation, hydrocarbon cracking, removal of alcohols to form olefins, formation of methylamines from methanol and ammonia, and partial oxidation of methane to methanol, wherein the catalyst composition comprises an intergrown zeolite material according to any one of embodiments 30-41.
[0118] Embodiment 52: A zeolitic material having a CHA crystalline framework, wherein the crystals of the zeolitic material have a predominantly flake-like morphology as determined by scanning electron microscopy (SEM).
[0119] Embodiment 53: The zeolitic material of embodiment 52, wherein at least about 40% of the crystals have a flaky morphology as determined by scanning electron microscopy / energy dispersive X-ray spectroscopy (SEM / EDS).
[0120] Embodiment 54: The zeolitic material of embodiment 52 or 53, wherein at least about 70% by weight of the crystals have a flaked morphology.
[0121] Embodiment 55: The zeolitic material of any one of embodiments 52 to 54, wherein the crystals have an average length and width of about 0.3 to about 1.5 μm and an average thickness of less than about 0.050 μm.
[0122] Embodiment 56: The zeolitic material of any one of embodiments 52 to 55, wherein the average thickness is less than about 0.025 μm.
[0123] Embodiment 57: The zeolitic material of any one of embodiments 52 to 56, wherein the crystal aspect ratio is greater than about 20.
[0124] Embodiment 58: The zeolitic material of any one of embodiments 52 to 57, wherein the crystal aspect ratio is from about 20 to about 40.
[0125] Embodiment 59: The zeolitic material of any one of embodiments 52 to 58, wherein the zeolitic material has a silica to alumina molar ratio (SAR) of from about 2 to about 60.
[0126] Embodiment 60: The zeolitic material of any one of embodiments 52 to 59, wherein the SAR is from about 10 to about 30.
[0127] Embodiment 61: The zeolitic material of any one of embodiments 52 to 60, wherein the zeolitic material has a silica to potassium molar ratio of less than about 20.
[0128] Embodiment 62: The zeolitic material of any one of embodiments 52 to 61, wherein the molar ratio of silica to potassium is from about 12 to about 17.
[0129] Embodiment 63: A method for synthesizing a zeolitic material having a CHA crystalline framework and a predominantly flaky morphology, the method comprising: preparing a mixture of water, an aluminum source, a silicon source, an organic structure directing agent, and an inorganic structure directing agent to form a synthesis gel, the inorganic structure directing agent comprising potassium cations; and subjecting the synthesis gel to a crystallization process to crystallize the zeolitic material.
[0130] Embodiment 64: The method of embodiment 63, wherein preparing comprises a first mixing step comprising adding an organic structure directing agent, an inorganic structure directing agent, and a source of aluminum to water to form an aluminum-containing aqueous solution and mixing the aqueous solution for a first period of time; and a second mixing step comprising adding a source of silicon to the aluminum-containing aqueous solution and mixing for a second period of time to form an aluminosilicate-containing solution.
[0131] Embodiment 65: The method of embodiment 63 or 64, wherein the first and second periods are each independently from about 1 second to about 24 hours.
[0132] Embodiment 66: The method of any one of embodiments 63 to 65, wherein the first and second mixing steps are carried out at a temperature of from about 20°C to about 100°C.
[0133] Embodiment 67: The method of any one of embodiments 63 to 66, wherein the crystallization process comprises mixing the synthesis gel at a temperature of about 100°C to about 200°C for a time period of about 12 hours to about 6 days.
[0134] Embodiment 68: The method of any one of embodiments 63 to 67, wherein the temperature is from about 160°C to about 180°C.
[0135] Embodiment 69: The method of any one of embodiments 63 to 68, further comprising filtering any crystals formed during the heating step.
[0136] Embodiment 70: The method of any one of embodiments 63 to 69, wherein the organic structure directing agent is selected from the group consisting of N,N,N-trimethyl-1-adamantylammonium hydroxide (TMAdaOH), trimethylcyclohexylammonium hydroxide, tetraethylammonium hydroxide, benzyltrimethylammonium hydroxide, 1,1,3,5-tetramethylpiperidinium hydroxide, choline hydroxide, N,N-dimethylpiperidinium hydroxide, trimethyl-2-ammonium exo-norbornane, and N-methyl-3-quinuclidinol.
[0137] Embodiment 71: The method of any one of embodiments 63 to 70, wherein the organic structure directing agent is TMAdaOH.
[0138] Embodiment 72: The method of any one of embodiments 63 to 71, wherein the inorganic structure directing agent is potassium hydroxide.
[0139] Embodiment 73: The method of any one of embodiments 63 to 72, wherein the amount of TMAdaOH and the amount of potassium cations present in the synthesis gel are such that the molar ratio of potassium cations to TMAdaOH is greater than or equal to about 10.
[0140] Embodiment 74: The method of any one of embodiments 63 to 73, wherein the molar ratio of potassium cations to TMAdaOH is from about 15 to about 50.
[0141] Embodiment 75: The method of any one of embodiments 63 to 74, wherein the amount of TMAdaOH and the amount of silicon source present in the synthesis gel are such that the molar ratio of TMAdaOH to silicon atoms is less than about 0.05.
[0142] Embodiment 76: The method of any one of embodiments 63 to 75, wherein the molar ratio of TMAdaOH to silicon atoms is from about 0.05 to about 0.01.
[0143] Embodiment 77: The method of any one of embodiments 63 to 76, wherein the source of aluminum is a zeolite, aluminum isopropoxide, or aluminum hydroxide.
[0144] Embodiment 78: The method of any one of embodiments 63 to 77, wherein the source of aluminum is aluminum hydroxide.
[0145] Embodiment 79: The method of any one of embodiments 63 to 78, wherein the source of silicon is colloidal silica, silicon alkoxide, fumed silica, amorphous silica, or an aluminosilicate.
[0146] Embodiment 80: The method of any one of embodiments 63 to 79, wherein the source of silicon is colloidal silica.
[0147] Embodiment 81: The method of any one of embodiments 63 to 80, wherein the silica-to-alumina ratio (SAR) of the synthesis gel is selected to provide a zeolitic material having an SAR of from about 2 to about 60.
[0148] Embodiment 82: The method of any one of embodiments 63 to 81, wherein the silica-to-alumina ratio (SAR) of the synthesis gel is selected to provide a zeolitic material having an SAR of from about 10 to about 30.
[0149] Embodiment 83: A zeolitic material having a CHA crystalline framework and a predominantly flaky morphology as determined by scanning electron microscopy / energy dispersive X-ray spectroscopy (SEM / EDS), prepared by the method of any one of embodiments 63 to 84.
[0150] Embodiment 84: Nitrogen oxides (NO x 84. A selective catalytic reduction (SCR) catalyst effective for the mitigation of CO₂ emissions from diesel engines, wherein the SCR catalyst comprises the zeolitic material of any one of embodiments 52-62 or embodiment 83 promoted with a promoter metal.
[0151] Embodiment 85: The SCR catalyst of embodiment 84, wherein the promoter metal is present in an amount of about 1.0 wt. % to about 10 wt. %, calculated as promoter metal oxide, based on the total weight of the SCR catalyst.
[0152] Embodiment 86: The SCR catalyst of embodiment 84 or 85, wherein the promoter metal is present in an amount of about 4 to about 6 weight percent.
[0153] Embodiment 87: The SCR catalyst of any one of embodiments 84 to 86, wherein the promoter metal is a transition metal.
[0154] Embodiment 88: The SCR catalyst of any one of embodiments 84-87, wherein the promoter metal is selected from iron, copper, manganese, and combinations thereof.
[0155] Embodiment 89: The SCR catalyst of any one of embodiments 84-88, wherein the promoter metal is selected from iron, copper, and combinations thereof.
[0156] These and other features, aspects, and advantages of the present disclosure will become apparent in the following detailed description taken in conjunction with the accompanying drawings, which are briefly described below. The present invention includes any combination of two, three, four, or more of the above-described embodiments, and any combination of two, three, four, or more features or elements described in this disclosure, regardless of whether such features or elements are explicitly combined in the description of a particular embodiment herein. The present disclosure is intended to be read as a whole such that any separable features or elements of the disclosed invention, in any of its various aspects and embodiments, should be considered as intended to be combinable unless the context clearly indicates otherwise. Other aspects and advantages of the present invention will become apparent hereinafter. [Brief explanation of the drawings]
[0157] To provide an understanding of embodiments of the present invention, reference is made to the accompanying drawings, which are not necessarily drawn to scale, and in which reference numerals refer to components of exemplary embodiments of the present invention. The drawings are merely illustrative and should not be construed as limiting the present invention. The disclosure described herein is illustrated in the accompanying drawings by way of example, and not by way of limitation. For simplicity and clarity of illustration, features shown in the drawings have not necessarily been drawn to scale. For example, the dimensions of some features may be exaggerated relative to other features for clarity. Furthermore, where considered appropriate, reference numerals may be repeated among the drawings to indicate corresponding or analogous elements.
[0158] [Figure 1ab] Depiction of the connectivity modes of the CHA and AEI backbones, respectively. [Figure 2] FIG. 1 is a perspective view of a honeycomb-type substrate that may include a catalyst (e.g., selective catalytic reduction catalyst) washcoat composition according to the present disclosure. [Figure 3a] 3 is an enlarged cross-sectional cutaway view of FIG. 2, where the honeycomb substrate represents a wall-flow filter substrate. [Figure 3b] 1 is a cross-sectional view of one embodiment of a layered catalyst article of the present disclosure. [Figure 3c] 1 is a cross-sectional view of one embodiment of a compartmentalized catalytic article of the present disclosure. [Figure 3d] 1 is a cross-sectional view of one embodiment of a layered compartmentalized catalyst article of the present disclosure. [Figure 4] 1 is a schematic diagram of one embodiment of an emissions treatment system utilizing the catalytic article of the present disclosure. [Figure 5abcd] X-ray diffraction patterns of CHA-type zeolites synthesized using Al(Oi-Pr)3 with Si / Al=15 and various ratios of Na+ / TMAda+. [Figure 6] 1 is a graph of the fraction of paired Al measured by Co 2+ exchange as a function of the number of paired Al predicted for a random Al distribution according to Lowenstein's law. [Figure 7abcdefgh] X-ray diffraction patterns of CHA synthesized with various K+ / TMAda+ ratios. [Figure 8abcd] 1 shows X-ray diffraction patterns of zeolites synthesized using Al(Oi-Pr)3 with Si / Al=15 and various ratios of K+ / TMAda+. [Figure 8e] 1 is an X-ray diffraction pattern of a commercially available MFI-type zeolite with a Si / Al ratio of 43. [Figure 9abcdefgh] Scanning electron micrographs at 1330x magnification of CHA synthesized at various K+ / TMAda+ ratios. [Figure 10] 1 is an energy dispersive X-ray spectroscope showing elemental analysis of two different high silica (1) and low silica (2) phases observed for one embodiment of the present disclosure synthesized at K+ / TMAda+=20. [Figure 11ab] 1A-1B are SEM micrographs of an embodiment of the present disclosure with K+ / TMAda+=1 taken at (a) 1300x and (b) 5000x magnification. [Figure 12ab]1A-1C are SEM micrographs of an embodiment of the present disclosure with K+ / TMAda+=2 taken at (a) 1250x and (b) 4800x magnification. [Figure 13ab] 1A-1C are SEM micrographs of an embodiment of the present disclosure synthesized with K+ / TMAda+=3 taken at (a) 1250x and (b) 5000x magnification. [Figure 14ab] 1A-1C are SEM micrographs of an embodiment of the present disclosure synthesized with K+ / TMAda+=4 taken at (a) 1250x and (b) 5000x magnification. [Figure 15ab] 1A-1C are SEM micrographs of an embodiment of the present disclosure synthesized with K+ / TMAda+=5 taken at (a) 1250x and (b) 5000x magnification. [Figure 16ab] 1A-1C are SEM micrographs of an embodiment of the present disclosure synthesized with K+ / TMAda+=10 taken at (a) 1400x and (b) 5900x magnification. [Figure 17ab] 1A-1C are SEM micrographs of an embodiment of the present disclosure synthesized with K+ / TMAda+=15 taken at (a) 1300x and (b) 5100x magnification. [Figure 18ab] 1A-1C are SEM micrographs of an embodiment of the present disclosure synthesized with K+ / TMAda+=20 taken at (a) 1700x and (b) 4900x magnification. [Figure 19] 1 is a graph showing Ar adsorption (filled circles) and desorption (open circles) isotherms at 87 K for one embodiment of the present disclosure synthesized with K+ / TMAda+=2. [Figure 20] 1 is a graph showing Ar adsorption (filled circles) and desorption (open circles) isotherms at 87 K for one embodiment of the present disclosure synthesized at K+ / TMAda+=15. [Figure 21a] Graph of the number of TMAda+ per CHA cage as measured by TGA and the amount of Na+ retained per CHA cage as measured by AAS as a function of the Na+ / TMAda+ ratio in the synthetic medium. [Figure 21b]Graph of the number of TMAda+ per CHA cage as measured by TGA and the amount of K+ retained per CHA cage as measured by AAS as a function of the K+ / TMAda+ ratio in the synthesis medium. [Figure 21c] 1 is a graph of the number of TMAda+ per CHA cage as a function of the amount of K+ or Na+ retained in the crystalline CHA product. [Figure 22a] 1 is a scanning electron microscope (SEM) photograph of a comparative example having a CHA skeletal structure. [Figure 22b] 1 is a scanning electron microscope (SEM) micrograph of another comparative example having a CHA backbone structure. [Figure 22cd] 1 is a scanning electron microscope (SEM) micrograph of an embodiment of the present disclosure. [Figure 23] 1 is a transmission electron microscope (TEM) image of one embodiment of the present disclosure. [Figure 24] 1 is a TEM single area diffraction pattern (SADP) for one embodiment of the present disclosure. [Figure 25a] 1 is an X-ray diffraction pattern for a comparative example having a CHA backbone structure. [Figure 25b] 1 is an X-ray diffraction pattern for another comparative example having a CHA backbone structure. [Figure 25cd] 1 is an X-ray diffraction pattern for an embodiment of the present disclosure. [Figure 26] 1 is a line graph of NOx conversion versus temperature for an SCR article of the present disclosure. DETAILED DESCRIPTION OF THE INVENTION
[0159] Before describing some exemplary embodiments of the invention, it is to be understood that the invention is not limited to the details of construction or process steps set forth in the following description. The invention is capable of other embodiments and of being practiced or carried out in various ways. Although the invention herein has been described with reference to particular embodiments, it is to be understood that these embodiments are merely illustrative of the principles and applications of the present invention. It will be apparent to those skilled in the art that various modifications and variations can be made to the disclosed method and apparatus without departing from the spirit and scope of the invention. Thus, it is intended that the present invention cover modifications and variations that come within the scope of the appended claims and their equivalents.
[0160] References throughout this specification to "one embodiment," "a particular embodiment," "one or more embodiments," or "an embodiment" mean that a particular feature, structure, material, or characteristic described in connection with an embodiment is included in at least one embodiment of the invention. Thus, the appearances of phrases such as "in one or more embodiments," "in a particular embodiment," "in one embodiment," or "in an embodiment" in various places throughout this specification are not necessarily all referring to the same embodiment of the invention. Furthermore, particular features, structures, materials, or characteristics may be combined in any suitable manner in one or more embodiments.
[0161] The following definitions are provided for terms used in this disclosure.
[0162] The articles "a" and "an" are used herein to refer to one or to more than one (ie, to at least one) of the grammatical object of the article.
[0163] Any ranges cited herein are inclusive.
[0164] The term "about" is used throughout this specification to express and account for small variations. For example, the term "about" can refer to ±5% or less, e.g., ±2% or less, ±1% or less, ±0.5% or less, ±0.2% or less, ±0.1% or less, or ±0.05% or less. All numerical values are modified by the term "about," whether or not explicitly stated. It is understood that values modified by the term "about" include the specific value. For example, "about 5.0" is inclusive of 5.0.
[0165] "AMOx" refers to a selective ammonia oxidation catalyst, which is a catalyst containing one or more metals (typically, but not limited to, Pt) and an SCR catalyst suitable for converting ammonia to nitrogen.
[0166] The terms "catalyst" or "catalyst material" or "catalyst composition" or "catalytic material" refer to a material that promotes a reaction. To produce a catalytic article, a substrate disclosed herein is coated with a catalyst composition. The coating is a "catalyst coating composition" or "catalyst coating." The terms "catalyst composition" and "catalyst coating composition" are synonymous.
[0167] "CSF" refers to a catalyzed soot filter, which is a wall-flow monolith. Wall-flow filters consist of alternating inlet and outlet channels, with the inlet channel inserted into the outlet end and the outlet channel inserted into the inlet end. The soot-carrying exhaust gas flow entering the inlet channel is passed through the filter wall before exiting the outlet channel. In addition to soot filtration and regeneration, the CSF may carry an oxidation catalyst to oxidize CO and HC to CO2 and HO or NO to NO2 to accelerate downstream SCR catalysts or promote soot particle oxidation at lower temperatures. When positioned after the LNT catalyst, the CSF can also perform H2S oxidation, suppressing H2S emissions during the LNT desulfurization process.
[0168] "DOC" refers to a diesel oxidation catalyst that converts hydrocarbons and carbon monoxide in the exhaust gas of a diesel engine. Typically, a DOC contains one or more platinum group metals, such as palladium and / or platinum, a support material, such as alumina, a zeolite for HC storage, and optionally a promoter and / or stabilizer.
[0169] "GDI" refers to a gasoline direct injection gasoline engine operating under lean-burn conditions.
[0170] "LNT" refers to a platinum group metal, ceria, and NO under lean conditions. x A catalyst containing an alkaline earth metal trap material (e.g., BaO or MgO) suitable for adsorbing lean NO x Under rich conditions, NO x is released and reduced to nitrogen.
[0171] A "molecular sieve" is a framework material that can be used as a catalyst, for example in particulate form, in combination with one or more promoter metals. Molecular sieves are materials based on an extensive three-dimensional network of oxygen ions, generally containing tetrahedral sites and having a substantially uniform pore distribution, with an average pore size of 20 angstroms (Å) or less. The pore size is defined by the ring diameter.
[0172] "NO x The term "refers to nitrogen oxide compounds such as NO or NO2.
[0173] The terms "on" and "above" in reference to coating layers can be used interchangeably. The term "directly on" means in direct contact. Although the disclosed articles, in certain embodiments, are referred to as including one coating layer "on" a second coating layer, such language is intended to encompass embodiments having intervening layers where direct contact between the coating layers is not required (i.e., "on" is not equivalent to "directly on").
[0174] As used herein, the term "selective catalytic reduction" (SCR) refers to a catalytic process that uses a nitrogenous reductant to reduce nitrogen oxides to dinitrogen (N). As used herein, "nitrogen oxides" and "NO x The term "oxides of nitrogen" refers to oxides of nitrogen.
[0175] "SCRoF" refers to an SCR catalyst composition coated directly onto a wall-flow filter.
[0176] As used herein, the term "structure directing agent" refers to a compound that is present during the crystallization of a zeolite and helps direct the formation of a desired crystalline structure (e.g., CHA).
[0177] As used herein, the term "substrate" refers to a monolithic material onto which a catalyst composition, i.e., a catalyst coating, is disposed, typically in the form of a washcoat. In one or more embodiments, the substrate is a flow-through monolith and a monolithic wall-flow filter. The washcoat is formed by preparing a slurry containing a specific solids content (e.g., 30% to 90% by weight) of catalyst in a liquid, which is then coated onto the substrate and dried to provide a washcoat layer.
[0178] Reference to a "monolithic substrate" means a unitary structure that is homogeneous and continuous from the inlet to the outlet.
[0179] "Washcoat" has its conventional meaning in the art of a thin, adherent coating of material (e.g., catalyst) applied to a "substrate," e.g., a honeycomb flow-through monolith substrate or a filter substrate that is sufficiently porous to allow the passage of the gas stream to be treated. As used herein, and as described in Heck, Ronald, and Farrauto, Robert, Catalytic Air Pollution Control, New York: Wiley-Interscience, 2002, pp. 18-19, a washcoat layer comprises a compositionally distinct layer of material disposed on the surface of a monolithic substrate or an underlying washcoat layer. A substrate can contain one or more washcoat layers, and each washcoat layer can differ in some aspect (e.g., the physical properties of the washcoat, such as particle size or crystallite phase, can differ) and / or the chemical catalytic function can differ.
[0180] Zeolites are a type of "molecular sieve"—framework materials that can be used as catalysts, for example, in particulate form and in combination with one or more promoter metals. Molecular sieves are oxygen ion-based materials with an extensive three-dimensional network structure that generally contains tetrahedral sites and has a substantially uniform pore distribution with an average pore size of 20 Å or less. The pore size is defined by the ring size.
[0181] As used herein, the term "zeolite" refers to a specific example of a molecular sieve containing silicon and aluminum atoms. Zeolites are crystalline materials with fairly uniform pore sizes ranging from about 3 to 10 angstroms in diameter, depending on the type of zeolite and the type and amount of cations contained in the zeolite lattice.
[0182] Zeolites are understood to be aluminosilicates with an open three-dimensional framework structure composed of corner-sharing TO4 (where T is Al or Si) tetrahedra. Anionic framework charge-balancing cations are loosely associated with framework oxygens, and the remaining pore volume is filled with water molecules. Non-framework cations are generally exchangeable, and water molecules are removable.
[0183] In certain embodiments, reference can be made to an "aluminosilicate zeolite" framework type, which limits the material to zeolites that do not contain phosphorus or other metals substituted in the framework, while the broader term "zeolite" is intended to include aluminosilicates and aluminophosphates. In some embodiments, the zeolite is an aluminosilicate zeolite. The term "aluminophosphate" refers to another specific example of a zeolite that contains aluminum and phosphate atoms. Aluminophosphates are crystalline materials with fairly uniform pore sizes. In some embodiments, the zeolite is a silicoaluminophosphate. Silicoaluminophosphate zeolites contain SiO / AlO / PO tetrahedra and are referred to as "SAPO." Non-limiting examples of SAPOs include SAPO-34 and SAPO-44.
[0184] Zeolites generally contain a silica-to-alumina (SAR) molar ratio of 2 or greater. While zeolites for use in the disclosed catalyst compositions are not particularly limited with respect to their SAR value, the particular SAR value associated with a zeolite can, in some embodiments, affect the SCR performance of the catalyst composition into which it is incorporated (e.g., especially after aging). In some embodiments, the SAR value of the zeolite ranges from about 5 to about 100, or from about 5 to about 50. In some embodiments, the SAR is from about 5 to about 25, and in other embodiments, the SAR is from about 10 to about 15.
[0185] Zeolites can be classified by the framework topology that defines their structure. As previously referenced herein, this disclosure specifically relates to materials prepared from zeolites having a chabazite (CHA) framework. Zeolite CHA framework-type molecular sieves have the approximate formula: (Ca,Na,K,Mg)AlSiO 126H2O (e.g., hydrated calcium aluminum silicate). Three synthetic forms of zeolite CHA-framework type molecular sieves are described in "Zeolite Molecular Sieves" by D.W. Breck, published by John Wiley & Sons in 1973, which is incorporated by reference. The three synthetic forms reported by Breck are Zeolite KG, described in J. Chem. Soc., p. 2822 (1956), Barrer et al.; Zeolite D, described in British Patent No. 868,846 (1961); and Zeolite R, described in U.S. Pat. No. 3,030,181. The synthesis of another synthetic form of the zeolite CHA framework type, SSZ-13, is described in U.S. Pat. No. 4,544,538, which is incorporated by reference. In certain embodiments, the CHA framework zeolite is selected from the group consisting of SSZ-13, SSZ-62, natural chabazite, Zeolite KG, Linde D, Linde R, LZ-218, LZ-235, LZ-236, ZK-14, SAPO-34, SAPO-44, SAPO-47, and ZYT-6.
[0186] Zeolites are composed of secondary building units (SBUs) and composite building units (CBUs) and occur in many different framework structures. Secondary building units contain up to 16 tetrahedral atoms and are not chiral. Composite building units are not necessarily achiral and cannot necessarily be used to construct the entire framework. The CHA framework has "double 6-ring" (d6r) secondary building units. The d6r secondary building unit has 12 tetrahedral atoms and is created by joining two "single s6r units," with the "6" representing the position of the tetrahedral silicon and aluminum atoms and the oxygen atom located between the tetrahedral atoms.
[0187] CHA framework-type zeolites, including chabazite, can also be described as "small-pore zeolites." Small-pore zeolites contain channels defined by up to eight tetrahedral atoms. The term "eight-ring" zeolite refers to a zeolite with eight-ring pore openings and double-six-ring (d6r) secondary structural units, resulting in a cage-like structure resulting from the connection of double-six-ring structural units by four rings. The framework structural type can be confirmed by scanning electron microscopy (SEM) or transmission electron microscopy (TEM). Zeolites of a given type have a specific arrangement of such structural units. For example, in the case of typical CHA framework-type zeolites, the periodic structural units are double-six-ring (d6r) layers, as referenced above. These layers, referred to herein as "A" and "B," are topologically identical, except that "B" is the mirror image of "A." Zeolites with a CHA framework result when layers of the same type stack on top of each other, for example, forming an AAAAAA stack or a BBBBBB stack. Zeolites with a different framework (AEI) result when layers "A" and "B" alternate, i.e., forming an ABABABAB stack. This difference between the CHA and AEI frameworks can be understood by referring to Figures 1a and 1b. Figure 1a shows the connection mode of the d6r units in the CHA framework, and Figure 1b shows the connection mode of the d6r units in the AEI framework, viewed along the x-axis. See the database of zeolite structures at http: / / america.iza-structure.org, incorporated herein by reference.
[0188] The zeolites of the present disclosure may contain intergrowths. A zeolite "intergrowth" may include at least two different zeolite framework types or two different zeolite compositions of the same framework type. According to the classification proposed by Rao and Thomas, two different types of intergrowths related to zeolites are epitaxial intergrowths and polymorphic intergrowths. See, for example, Rao, CNR and Thomas, JM: "Intergrowth Structures: The Chemistry of Solid-Solid Interfaces," Acc. Chem. Res. 1985, 13, 113-119. Epitaxy involves the oriented overgrowth of zeolite crystals by compositionally or structurally distinct zeolite phases, whereas polytypes occur when individual sheets of layered material stack in different orders. In "overgrown" zeolites, one framework structure grows on top of another. Thus, "overgrowth" represents a type of "intergrowth," while "intergrowth" is a genus.
[0189] Examples of epitaxy reported in the literature are the structural overgrowth of zeolite X on zeolite A (de Vos Burchart, et al., "Ordered overgrowth of zeolite X onto crystals of zeolite A", Zeolite 1989, 9, 423-435), zeolite P on zeolite (Breck, Zeolite Molecular Sieves: Structure, Chemistry and Use, John Wiley & Sons, New York, 1974), or FAU / EMT overgrowth materials (Goossens et al., "Synthesis and Characterization of Epitaxial FAU-on-EMT Zeolite Overgrowth Materials", Eur. J. Inorg. Chem. 2001, 1167-1181). Examples of compositional overgrowth can be found in the combination of ZSM-5 or ZSM-11 with silicalite-1 disclosed in U.S. Pat. No. 4,148,713, and in crystalline silicate particles, e.g., substantially aluminum-free ZSM-5 or ZSM-11, having an inner portion comprising an intermediate pore size crystalline silicate and an aluminum-containing isostructural outer shell, as disclosed in U.S. Pat. No. 4,394,362.
[0190] Polytyping is a more general intergrowth phenomenon in zeolite crystallization. It can be depicted as a stack of different structurally uniform domains within each individual crystal, without bond mismatch. Two or more types of domains may be structurally related, for example, when they exhibit different periodicities. This is often the case, for example, in FAU / EMT (disclosed, for example, in Anderson et al., "Intergrowths of Cubic and Hexagonal Polytypes of Faujasitic Zeolites", J. Chem. Soc. Chem. Commun. 1991, 1660-1664; and Treacy et al., "Intergrowth Segregation in FAU-EMT Zeolite Materials", Proc. R. Soc. Lond. A-Math. Phys. Eng. Sci. 1996, 452, 813-840) or MFI / MEL (disclosed, for example, in Thomas et al., "Direct, Real-space Determination of Intergrowths in ZSM-5 / ZSM-11 Catalysts", J. Chem. Soc. Chem. Commun. 1982, 1380-1383; and Millward et al., "Evidence for Semi-regularly Ordered Sequences of In ZSM-5 / ZSM11 zeolitic structures, the stacking occurs as alternating sheets of the same general structure (as disclosed in "Mirror and Inversion Symmetry Planes in ZSM-5 / ZSM11 Shape-selective Zeolitic Catalysts," J. Chem. Soc. Faraday Trans. 1983, 79, 1075-1082). In some cases, the stacking occurs as alternating sheets of the same general structure, as in MAZ / MOR (as disclosed, for example, in Leonowicz et al., "Proposed synthetic zeolite ECR-1 structure gives a new zeolite framework topology," Nature 1987, 329, 819-821).The stacking pattern can vary from a strict alternation to a domain arrangement with no periodicity at all.
[0191] Specifically, polytypes of materials in the ABC-6 zeolite family are well known as intergrowths. Examples of materials in the ABC-6 family include chabazite, offretite, erionite, gmelinite, sodalite, and levinite. The structure of ABC-6 zeolite materials can be represented as a stacking of layers containing planar 6-rings (6R), as described above. The 6R in one layer can be connected to the next layer of 6R in various ways. Three different positions of the 6R in a layer can be designated A, B, or C. The 6R in different layers can be connected parallel to each other (position A) or shifted (positions B and C), resulting in various frameworks belonging to the ABC-6 family. For example, offretite can be represented by three connected layers with a stacking sequence of AAB, while erionite contains six unique layers with a sequence of AABAAC. Stacking defects between one of these layers, in which the stacking sequence is slightly altered in some places, can easily occur, resulting in intergrowths of different framework types. When the AAB stacking sequence of an OFF zeolite is randomly replaced by AABAAC, or vice versa, it is called an ERI / OFF intergrowth, with the ERI and OFF framework types being the end members of the intergrowth series. Zeolite T and ZSM-34 are the most common examples. Examples of materials that can be intergrowthed with chabazite are zeolites with GME and AEI framework types. Another example is the CHA / AEI intergrowth disclosed, for example, in U.S. Patent Application Publication No. 2012 / 0184429, which is incorporated herein by reference in its entirety. Another example is the CHA / ERI intergrowth disclosed, for example, in European Patent Application Publication No. 3323785, which is incorporated herein by reference in its entirety.
[0192] The presence of intergrowths and their skeletal characterization can be confirmed by scanning electron microscopy (SEM) or transmission electron microscopy (TEM). Typically, in CHA-based materials, while SEM of intergrowths (typically exhibiting a cubic habit) in CHA-based materials reveals an increased amount of other morphologies (e.g., orthorhombic structures, as seen in AEI-based materials), indicating the presence of other characteristics (in this example, a CHA / AEI intergrowth). Quantification of the individual skeletal types can be obtained from SEM or TEM images.
[0193] Unless otherwise indicated, all parts and percentages are by weight. Unless otherwise indicated, "weight percent (wt%)" is based on the total composition, excluding volatile materials, i.e., dry solids content.
[0194] All methods described herein can be performed in any suitable order unless otherwise indicated herein or clearly contradicted by context. The use of any and all examples or exemplary language (e.g., "such as") provided herein is intended only to better describe the materials and methods and does not limit the scope unless otherwise claimed. No language in the specification should be construed as indicating any non-claimed element as essential to the practice of the disclosed materials and methods.
[0195] All U.S. patent applications, published patent applications and patents referenced herein are hereby incorporated by reference.
[0196] Chabazite synthesis method By way of non-limiting example, the zeolitic materials disclosed herein are prepared from a reaction mixture containing a source of organic structure directing agent (SDA), a source of inorganic structure directing agent, a source of silicon, a source of aluminum, and water.
[0197] Thus, in one aspect, there is provided a method for synthesizing a zeolite having a CHA crystalline framework, the method comprising preparing a mixture of water, an aluminum source, a silica source, a source of organic structure directing agent, and an inorganic structure directing agent to form a synthesis gel, where the inorganic structure directing agent is a source of potassium cations, and subjecting the synthesis gel to a crystallization process to crystallize chabazite-type zeolite.
[0198] In another aspect, there is provided a method for synthesizing a CHA-type zeolite having a predominantly flake-like morphology, the method comprising: preparing a mixture of water, an aluminum source, a silicon source, an OSDA, and an inorganic structure-directing agent comprising potassium cations to form a synthesis gel; and subjecting the synthesis gel to a crystallization process to crystallize a CHA-type zeolite having a predominantly flake-like morphology.
[0199] Each component of the above method is described in further detail below.
[0200] organic structure directing agent To prepare materials comprising CHA-type zeolites according to the disclosed methods, organic structure-directing agents (OSDAs), also referred to as "templates" or "templating agents," are used. OSDAs are organic molecules that guide or direct the molecular shape and pattern of the zeolite framework, e.g., by acting as a scaffold around which zeolite crystals form. After crystal formation, the OSDA is removed from the crystal's internal structure, leaving behind a molecularly porous aluminosilicate cage. Specifically, the methods provided herein generally involve the use of at least one OSDA conventionally understood to result in a CHA-type framework. The specific type of OSDA used can vary. In some embodiments, the OSDA is selected from cyclic amines and / or ammonium compounds. Examples include quaternary ammonium cations having substituents selected from the group consisting of alkyl, adamantyl, cyclohexyl, aromatic, and combinations thereof. As used herein, the term "quaternary ammonium cation" refers to an organic molecule containing a nitrogen atom with four substituents and thus a positive (cationic) charge. Quaternary ammonium cations are formed by the addition of anions, such as halides (e.g., Cl). - , Br - , I - ), hydrogen sulfate (HSO4 - ), or hydroxide (OH -) ions, referred to herein as "quaternary ammonium salts" or "quaternary ammonium compounds," which dissociate in solution into free quaternary ammonium cations and their respective anions. For example, in some embodiments, the CHA organic structure directing agent is selected from N,N,N-trimethyl-1-adamantammonium, N,N,N-trimethyl-2-adamantammonium, N,N,N-trimethylcyclohexylammonium, tetraethylammonium, benzyltrimethylammonium, N,N-dimethyl-3,3-dimethylpiperidinium, N,N-methylethyl-3,3-dimethylpiperidinium, N,N-dimethyl-2-methylpiperidinium, 1,1,3,5-tetramethylpiperidinium, 1,3,3,6,6-pentamethyl-6-azonio-bicyclo(3.2.1)octane, or a trimethyl-2-ammonium exonorbornane compound, or N,N-dimethylcyclohexylamine, choline hydroxide, N-methyl-3-quinuclidinol, a bicyclic or tricyclic nitrogen-containing organic compound, or a combination of any of the foregoing amine or ammonium compounds. In some embodiments, the CHA structure directing agent is selected from the group consisting of N,N,N-trimethyl-1-adamantammonium compounds, N,N,N-trimethyl-2-adamantammonium compounds, N,N,N-trimethylcyclohexylammonium compounds, N,N-dimethyl-3,3-dimethylpiperidinium compounds, N,N-methylethyl-3,3-dimethylpiperidinium compounds, N,N-dimethyl-2-methylpiperidinium compounds, 1,3,3,6,6-pentamethyl-6-azonio-bicyclo(3.2.1)octane compounds, N,N-dimethylcyclohexylamine, bicyclic and tricyclic nitrogen-containing organic compounds, and combinations thereof.
[0201] Suitable SDAs are disclosed, for example, in "Zeolites and Related Microporous Materials: State of the Art 1994," "Studies of Surface Science and Catalysis," Vol. 84, pp. 29-36; "Novel Materials in Heterogeneous Catalysis," edited by Baker and Murrell, Chapter 2, pp. 14-24, May 1990; "J. Am. Chem. Soc.," 2000, 122, pp. 263-273; and U.S. Patent Nos. 4,544,538 and 6,709,644, all of which are incorporated herein by reference. In some embodiments, the quaternary ammonium cation is balanced with an anion selected from bromide, iodide, and hydroxide. In certain embodiments, the OSDA is N,N,N-trimethyl-1-adamantylammonium hydroxide (TMAdaOH).
[0202] The amount of OSDA present in the synthesis gel can vary. In some embodiments, the amount of OSDA present can be expressed in terms of its molar ratio to silicon. In some embodiments, the molar ratio of TMAdaOH to silicon is about 0.01 to about 0.2, such as from about 0.01, about 0.02, about 0.03, about 0.04, about 0.05, about 0.06, about 0.07, about 0.08, about 0.09, or about 0.1 to about 0.11, about 0.12, about 0.13, about 0.14, about 0.15, about 0.16, about 0.17, about 0.18, about 0.19, or about 0.2.
[0203] Inorganic Structure Directing Agents The source of the inorganic structure directing agent (SDA) can vary and in some embodiments can be an alkali metal cation such as sodium or potassium.
[0204] In certain embodiments, the inorganic structure directing agent (SDA) comprises a potassium cation. In certain embodiments, the inorganic SDA is a potassium cation.
[0205] In certain embodiments, potassium cations (K + The source of the inorganic SDA is an aqueous solution of potassium hydroxide, e.g., potassium oxide (KO). The amount of inorganic structure-directing agent (e.g., potassium hydroxide) added can vary. Notably, hydroxide ions are the only necessary mineralizer required in the reaction mixture, and the amount of hydroxide required in the synthesis gel can be provided by either an organic or inorganic structure-directing agent. In some embodiments, potassium hydroxide functions as the inorganic SDA and hydroxide ion source and is provided in an amount to ensure that the synthesis gel has a pH within a specific range. For example, in some embodiments, the pH is advantageously basic, e.g., about 12 to about 13. If desired, the hydroxide ion content can be supplemented with an additional hydroxide ion source, e.g., sodium hydroxide (NaOH), a quaternary ammonium hydroxide, e.g., tetramethylammonium hydroxide, or a combination thereof.
[0206] Surprisingly, CHA zeolites also contain Na + (Na + / TMAda + <2) than K + (K + / TMAda + We have discovered that crystallization from synthesis media containing inorganic to organic SDA ratios that are over an order of magnitude higher (<50) is possible. In some embodiments, the ratio of potassium cations to TMAda in the synthesis gel is from about 1, or about 2, to about 5, about 10, about 15, about 20, or about 50. In some embodiments, the ratio is from about 2 to about 10.
[0207] In some embodiments, the molar ratio of potassium to TMAdaOH in the synthesis gel is about 10 to about 50, for example, from about 10, about 15, about 20, or about 25, to about 30, about 25, about 40, about 45, or about 50.
[0208] In certain embodiments, the OH / Si molar ratio of the synthesis gel is about 0.5, and the molar ratio of potassium to TMAdaOH in the synthesis gel is about 10 to about 50.
[0209] In some embodiments, the hydroxide to silica (OH / Si) molar ratio in the synthesis gel is from about 0.2 to about 0.5, such as from about 0.2 or about 0.3 to about 0.4 or about 0.5.
[0210] In some embodiments, the potassium to silicon (K / Si) molar ratio in the synthesis gel is from about 0.2 to about 0.5, such as from about 0.2 or about 0.3 to about 0.4 or about 0.5.
[0211] The methods outlined herein advantageously do not use halide-containing compounds (e.g., fluoride or fluorine-containing compounds). Hydrofluoric acid (HF) is used in the reaction mixture to provide the AEI-CHA intergrowth. In this embodiment, the methods of the present disclosure do not use halogen- or halide-containing compounds, e.g., do not use fluorine or fluoride-containing compounds.
[0212] Aluminum Source The source of aluminum can vary. In some embodiments, the aluminum source is zeolitic. In other embodiments, the aluminum source is non-zeolitic. Thus, in some embodiments, the methods provided herein advantageously do not use zeolites to produce the materials of the present disclosure (although the methods are not so limited, and in some embodiments, zeolites can be used as the alumina source).
[0213] In some embodiments, the aluminum source is amorphous. For example, in certain embodiments, the aluminum source can be an amorphous source selected from aluminum salts (e.g., aluminum triisopropoxide or other alkoxides, aluminum hydroxide, aluminum nitrate, aluminum chloride, aluminum phosphate), aluminum metal, amorphous aluminum oxide, or amorphous aluminosilicates. In other embodiments, the aluminum source is crystalline, such as crystalline alumina or zeolite. In certain embodiments, the aluminum source can be selected from aluminum triisopropoxide or other alkoxides, aluminum hydroxide, aluminum nitrate, aluminosilicates, aluminum chloride, aluminum phosphate, aluminum oxide, or aluminum metal. In some embodiments, the aluminum source is aluminum triisopropoxide or aluminum hydroxide. In some embodiments, the aluminum source is aluminum hydroxide.
[0214] silicon source The silicon source can also vary. In various embodiments, silicon is provided by one or more of precipitated silica, colloidal silica, silica gel, silicon hydroxide, silicon alkoxide, amorphous silica, aluminosilicate, fumed silica, or silicate, such as alkali metal silicate. In some embodiments, the silicon source is colloidal silica.
[0215] In some embodiments, the amounts of silicon and aluminum present in the synthesis gel are selected so that the calculated SAR of the starting composition is in the range of about 1 to about 100, e.g., about 2 to 60. In some embodiments, the SAR of the starting composition is in the range of about 10 to about 40. In some embodiments, the SAR of the starting composition is in the range of about 20 to about 35. Those skilled in the art will recognize that the as-synthesized SAR and the SAR of the final zeolite are not necessarily the same, and will know how to select the as-synthesized SAR to achieve a desired SAR in the final zeolite. In some embodiments, the target SAR for CHA-type zeolite is about 2 to about 60, about 10 to about 30, or about 15 to about 25.
[0216] In one embodiment, the amounts of silica and alumina present in the synthesis gel are selected so that the calculated SAR of the starting composition is in the range of about 10 to about 100, e.g., about 50 to about 80. Those skilled in the art will recognize that the as-synthesized SAR and the SAR of the final zeolite are not necessarily the same, and will know how to select as-synthesized SAR values to achieve a desired SAR in the final zeolite. In some embodiments, the target ratio for CHA-type zeolite is Si / Al=15.
[0217] In some embodiments, the ratio of silicon source to aluminum source to TMAda to potassium cation source to water can be represented by 1 SiO / 0.033 AlO / X TMAdaOH / 0.5*(0.5-X)KO / 44 H0, where inorganic SDA (K + ) organic SDA (TMAda + The ratio of X to X can be controlled by varying the value of X between about 0.01 and about 0.25. For example, X can be from about 0.01, about 0.02, about 0.03, about 0.04, about 0.05, about 0.06, about 0.07, about 0.08, or about 0.09 to about 0.1, about 0.15, about 0.2, or about 0.25.
[0218] mixture As described above, the method generally includes forming a reaction mixture containing water, an aluminum source, a silicon source, an organic structure directing agent (OSDA), and an inorganic structure directing agent to form an aluminosilicate-containing solution, referred to herein as a "synthesis gel" or "gel," and subjecting the synthesis gel to a crystallization process to crystallize the zeolite. Typically, the synthesis gel has a high solids content (e.g., about 15% or more, or about 20% or more).
[0219] In some embodiments, the method for synthesizing a zeolite having a CHA crystalline framework includes a first mixing step including adding a source of organic structure directing agent, a source of inorganic structure directing agent, and a source of aluminum to water to form an aluminum-containing aqueous solution, and mixing the aqueous solution for a first period of time.
[0220] The mixing step can be carried out for various times. The time for mixing can range from 1 second to about 24 hours. For example, the time can be from about 1 second to about 1 minute, or from about 1 minute, about 5 minutes, about 10 minutes, or about 15 minutes, to about 30 minutes, about 45 minutes, or about 1 hour, or from about 1 hour, about 2 hours, about 3 hours, about 4 hours, about 5 hours, or from about 6 hours, to about 12 hours, or about 24 hours. In some embodiments, the time is about 2 hours.
[0221] In some embodiments, the mixing can be performed in separate, distinct steps. Thus, in some embodiments, the method includes a first mixing step that includes adding OSDA, SDA, and an aluminum source to water to form an aluminum-containing aqueous solution and mixing the aqueous solution for a first period of time.
[0222] The first time period can range from 1 second to about 24 hours. For example, the first time period can range from about 1 second to about 1 minute, or can range from about 1 minute, about 5 minutes, about 10 minutes, or about 15 minutes to about 30 minutes, about 45 minutes, or about 1 hour, or from about 1 hour, about 2 hours, about 3 hours, about 4 hours, about 5 hours, or about 6 hours to about 12 hours, or about 24 hours. In some embodiments, the first time period is about 15 minutes.
[0223] The first mixing step can be carried out at a variety of temperatures, in some embodiments, the mixing is carried out at room temperature, in some embodiments, the mixing is carried out at an elevated temperature (e.g., a temperature above room temperature, such as from about 25°C to about 100°C).
[0224] In some embodiments, the method includes a second mixing step that includes adding a source of silicon to the aluminum-containing aqueous solution and mixing for a second period of time to form a synthesis gel.
[0225] The second time period can range from 1 second to about 24 hours. For example, the second time period can be from about 1 second to about 1 minute, or from about 1 minute, about 5 minutes, about 10 minutes, or about 15 minutes, to about 30 minutes, about 45 minutes, or about 1 hour, or from about 1 hour, about 2 hours, about 3 hours, about 4 hours, about 5 hours, or about 6 hours, to about 12 hours, or about 24 hours. In some embodiments, the second time period is about 2 hours.
[0226] The second mixing step can be carried out at a variety of temperatures, in some embodiments, the mixing is carried out at room temperature, in some embodiments, the mixing is carried out at an elevated temperature (e.g., a temperature above room temperature, such as from about 25°C to about 100°C).
[0227] In some embodiments, the first and second times are each independently from about 1 second to about 24 hours. In some embodiments, the first time is from about 5 minutes to about 1 hour. In some embodiments, the second time is from about 5 minutes to about 1 hour.
[0228] In some embodiments, the first and second mixing steps are carried out at a temperature of about 20°C to about 100°C. In some embodiments, the first and second mixing steps are carried out at a temperature of about 20°C to about 50°C. In some embodiments, the first and second mixing steps are carried out at a temperature of about 20°C to about 30°C.
[0229] Crystallization In some embodiments, the synthesis gel is then subjected to a crystallization process to crystallize a chabazite-type zeolite having a controlled aluminum distribution. Crystallization conditions are generally selected to promote the formation of a solid precipitate containing zeolite crystals. Typically, the crystallization process involves mixing the synthesis gel at an elevated temperature for a period of time. Generally, the reaction mixture described hereinabove is heated with stirring in a pressure vessel to produce the desired CHA crystalline product.
[0230] In some embodiments, the time can range from about 24 hours to about 6 days. For example, the time can range from about 24 hours, about 30 hours, or about 36 hours to about 2 days, about 3 days, about 4 days, about 5 days, or about 6 days. In some embodiments, the third time is about 3 days. In some embodiments, the time is about 6 days. The crystallization process can be carried out at various temperatures at the corresponding autogenous pressure, and in some embodiments, the crystallization process is carried out at a temperature in the range of about 100°C to about 200°C, e.g., about 140°C to about 200°C, or about 140°C to about 180°C. In some embodiments, the temperature is about 140°C to about 160°C.
[0231] After cooling the synthesis gel, the precipitate containing the zeolite material is then filtered off and optionally subjected to further processing. Optionally, the product can be centrifuged. Organic additives can be used to aid in handling and isolating the solid product. The precipitate can be filtered off, and the remaining mother liquor can be discarded or recycled, as disclosed, for example, in U.S. Patent Application Publication No. 2015 / 118150 by Yang et al., which is incorporated herein by reference. Spray drying is an optional step in the processing of the product.
[0232] In other embodiments, the synthesis gel is then subjected to a crystallization process to crystallize CHA-type zeolite having a predominantly flake-like morphology. Crystallization conditions are generally selected to promote the formation of a solid precipitate containing CHA-type zeolite crystals. Typically, the crystallization process involves mixing the synthesis gel at an elevated temperature for a period of time. Generally, the reaction mixture described hereinabove is heated with stirring in a pressure vessel to produce the desired CHA crystalline product. In some embodiments, the crystallization optionally further comprises adding zeolite seed crystals to the synthesis gel to promote the formation of the desired crystalline structure. In some embodiments, the seed crystals have a CHA framework. In some embodiments, the seed crystals are calcined and Na + It is a CHA-type zeolite.
[0233] In some embodiments, the time can range from about 12 hours to about 6 days. For example, the time can range from about 12 hours, about 18 hours, about 24 hours, about 30 hours, or about 36 hours to about 2 days, about 3 days, about 4 days, about 5 days, or about 6 days. In some embodiments, the third time is about 3 days. In some embodiments, the time is about 6 days. The crystallization process can be carried out at various temperatures at the corresponding autogenous pressure, and in some embodiments, the crystallization process is carried out at a temperature in the range of about 100°C to about 200°C, e.g., about 140°C to about 200°C, or about 140°C to about 180°C. In some embodiments, the temperature is about 140°C to about 160°C.
[0234] After cooling the synthesis gel, the precipitate containing the zeolite material is then filtered off and optionally subjected to further processing. Optionally, the product can be centrifuged. Organic additives can be used to aid in handling and isolating the solid product. The precipitate can be filtered off, and the remaining mother liquor can be discarded or recycled, as disclosed, for example, in U.S. Patent Application Publication No. 2015 / 118150 by Yang et al., which is incorporated herein by reference. Spray drying is an optional step in the processing of the product.
[0235] Further processing The solid CHA-type zeolite product can be heat treated or calcined in air or nitrogen. Typical calcination temperatures are from about 400°C to about 850°C (e.g., from about 500°C to about 700°C) for a period of 1 to 10 hours. Following the initial calcination, the CHA-type zeolite product is primarily in the alkali metal form (e.g., K + form).
[0236] The zeolite obtained after calcination may be ion-exchanged to reduce the amount of alkali or to exchange with, for example, ammonium ions. In some embodiments, single or multiple ammonium ion exchanges are used to convert the NH4 + A morphology can be produced, which can be optionally further fired to produce H + Ion exchange methods are well known in the art and can be applied without departing from the scope of the claims. Ion exchange can be achieved, for example, by treatment with aqueous ammonium chloride.
[0237] Characteristics of CHA-type zeolite In some embodiments, the CHA zeolite crystals resulting from crystallization can be about 50 to about 100% crystalline. In some embodiments, the CHA zeolite crystals resulting from crystallization can be about 80% to about 99% crystalline, or about 90% to about 97% crystalline. The CHA zeolite product obtained from the disclosed method typically has an average crystal size of about 0.1 μm to a maximum of about 15 μm, for example, 0.1 μm to about 2 μm, or about 2 μm to 5 μm, or about 4 μm to about 8 μm, or about 10 μm to about 15 μm. The average crystal size can be measured, for example, using microscopy, such as scanning electron microscopy (SEM).
[0238] The CHA-type zeolite products obtained from the disclosed methods generally have unit cell volumes consistent with those reported in the literature (e.g., 2338 Å reported for silica-rich CHA). 3 (M.-J. Diaz-Cabanas et al., Chemical Communications, 1998, pp. 1881-1882) reported that the aluminum-rich CHA has a melting point of 2489 Å. 3 (OVYakubovich et al., Crystallography Reports, Vol. 50, No. 4, 2005, pp. 544-553).
[0239] The CHA-type zeolite product can also be characterized by its silica-to-alumina molar ratio (SAR). In one embodiment, the silica-to-alumina molar ratio in the CHA-type zeolite ranges from 2 to 60. In certain embodiments, the CHA-type zeolite product has an SAR of about 10 to about 30. In certain embodiments, the CHA-type zeolite product has an SAR of about 10 to about 15.
[0240] As described herein, depending on the amount of inorganic structure-directing agent added during zeolite crystallization, non-aluminum inorganic cations can reside in extra-framework positions of the zeolite. For purposes of this disclosure, extra-framework positions should be understood to mean positions that are not covalently bonded to four atoms in the crystalline zeolite lattice. Atoms, ions, and complexes in extra-framework positions of the zeolite typically refer to those found in the pore space of the solid, and are not incorporated into the lattice framework itself. These non-aluminum inorganic cations include, but are not limited to, sodium, calcium, potassium, magnesium, cobalt, copper, and lithium cations, and combinations thereof. In such a scenario, only a portion of the aluminum atoms in the zeolite crystal lattice framework positions are in a dissociated configuration, and this portion cannot exchange with the divalent cations in the extra-framework positions.
[0241] It is therefore yet another object of the present disclosure to describe a different class of chabazite-type zeolite structures having controlled aluminum distribution, whereby due to the presence of non-aluminum inorganic cations in extra-framework positions of the zeolite, only a portion of the aluminum atoms in the crystal lattice framework positions of the zeolite framework are in a segregated configuration, which portion cannot combine with divalent cations in extra-framework positions. Surprisingly, according to the present disclosure, K + and TMAda + CHA-type zeolites crystallized from the mixture were found to have K+ cations displacing TMAda+ from the CHA cages, leading to the formation of mainly isolated Al sites within the same composition range.
[0242] In some embodiments, the CHA-type zeolites of the present disclosure have predominantly isolated Al sites, which have the formula Al-O(-Si-O) x-Al, where x≧3. In some embodiments, i.e., in the CHA-type zeolites of the present disclosure, the fraction of aluminum atoms at crystal lattice framework positions of the CHA-type zeolite framework in the isolated configuration ranges from 0.90 to 1.00. In some embodiments, the fraction of aluminum atoms at crystal lattice framework positions of the CHA-type zeolite framework in the isolated configuration ranges from about 0.95 to about 1.00.
[0243] In other embodiments, the CHA-type zeolites of the present disclosure have predominantly paired Al sites, which have the formula Al-O(-Si-O) x -Al, where x=1 or 2.
[0244] Intergrowth According to the present disclosure, it has surprisingly been found that organic and inorganic cations cooperate or compete for occupancy within the voids of CHA-type zeolites, resulting in, in some embodiments, intergrowths of crystalline phases (mixed domains). Thus, in some embodiments, zeolitic materials comprising intergrowths are provided, and the synthesis methods disclosed herein can be characterized as methods for preparing zeolites containing such intergrowths. Typically, the characteristics of zeolitic materials comprising intergrowths as disclosed herein can be described as primarily one type of framework. For example, in some embodiments, the disclosed zeolitic materials comprising intergrowths have the characteristics of a CHA framework and also include multiple intergrowth phases, each having a CHA framework and a different silica-to-alumina ratio.
[0245] The presence of intergrowths can be determined, for example, by powder diffraction patterns. Specifically, the experimental powder diffraction patterns for the intergrowths disclosed herein can be compared to simulated powder diffraction patterns, for example, using DIFFax, a computer program based on a mathematical model for simulating powder diffraction patterns from crystals containing planar defects, selected by and available from the International Zeolite Society, to simulate XRD powder patterns for intergrowth phases of zeolites. See Treacy et al., Proceedings of the Royal Chemical Society 1991, 433:499-520 and Treacy and Higgins, Collection of Simulated XRD Powder Patterns for Zeolites, Fifth Edition, Elsevier 2007, which are incorporated herein by reference in their entirety.
[0246] In some embodiments, peak broadening is observed in the XRD pattern compared to a physical mixture of the two phases. Such peak broadening may be observed as evidence of intergrowth (rather than intermixing) of the two phases. The presence of intergrowth with a CHA framework can be further confirmed in some embodiments by scanning electron microscopy (SEM) or transmission electron microscopy (TEM).
[0247] In some embodiments, the CHA-type zeolite product resulting from the disclosed methods is an intergrowth zeolite comprising a mixture of two different crystalline CHA phases that differ from each other in size and composition.
[0248] In some embodiments, the intergrowth zeolite comprises a first and a second CHA phase, and the first CHA phase and the second CHA phase each independently have a diameter of about 2338 Å. 3 ~2489Å 3and the unit cell volume of the first CHA phase is different from the unit cell volume of the second CHA phase. In some embodiments, the unit cell volumes of the first CHA phase and the second CHA phase are 2353 Å or less. 3 ~2411Å 3 The range is.
[0249] The ratio of these phases can vary. In some embodiments, the first CHA phase represents about 5% to about 95% of the intergrown zeolite. In one embodiment, the first CHA phase represents about 20-30% of the intergrown zeolite, and the second CHA phase represents about 70-80% of the intergrown zeolite. In some embodiments, the first CHA phase represents about 5% to about 95% of the intergrown zeolite, and the first CHA phase has a potassium cation to aluminum ratio greater than 0.5, and the second CHA phase has a potassium cation to aluminum ratio less than about 0.5. In some embodiments, the first CHA phase has a potassium cation to aluminum ratio of about 0.5 to about 1.6, e.g., from about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, or about 1.0 to about 1.1, about 1.2, about 1.3, about 1.4, or about 1.5. In some embodiments, the second CHA phase has a potassium cation to aluminum ratio of about 0.1 to about 0.5, e.g., from about 0.1, about 0.15, about 0.2, about 0.25, or about 0.3 to about 0.35, about 0.4, about 0.45, or about 0.5.
[0250] In some embodiments, the intergrowth zeolite comprises first and second CHA phases, the first and second CHA phases each independently having a silica-to-alumina ratio (SAR) of from about 4 to about 100, and the SAR of the first CHA phase is different from the SAR of the second CHA phase.
[0251] In some embodiments, the first CHA phase has a higher SAR than the second CHA phase. In some embodiments, the SAR of the first CHA phase is about 10 to about 40, and the SAR of the second CHA phase is about 6 to about 8. In some embodiments, the SAR of the first CHA phase is about 10 to about 20. In some embodiments, the SAR of the first CHA phase is about 10 to about 15.
[0252] In some embodiments, the first CHA phase comprises primarily potassium ions and the second CHA phase comprises primarily an organic directing agent.
[0253] In some embodiments, the first CHA phase and the second CHA phase have different lattice constants a0, c0, and unit cell volumes as determined from X-ray powder diffraction patterns.
[0254] In some embodiments, the first CHA phase, the second CHA phase, or both comprise a silicoaluminophosphate (SAPO) composition. In some embodiments, the SAPO composition is SAPO-34 or SAPO-44.
[0255] In some embodiments, the intergrowth zeolite crystal size is from about 0.1 to about 15 μm.
[0256] Flake-like form In some embodiments, CHA-type zeolites prepared as disclosed herein have a predominantly flake-like morphology. "Flake-like" means that CHA zeolite crystals are much longer and wider than they are thick. This morphology can be distinguished from plate-like morphology in that flake-like crystals can and are often observed in a folded configuration (but not in plate-like morphology). For example, see U.S. Pat. No. 9,981,852 to Choi et al. for a disclosure of CHA-type zeolites having a plate-like morphology. This patent is incorporated herein by reference in its entirety. CHA-type zeolite products resulting from the methods disclosed herein typically have an average crystal length of about 0.3 μm up to about 1.5 μm, e.g., about 0.3 to about 1 μm, or about 0.3 to about 0.5 μm. The CHA-type zeolite product resulting from the disclosed method typically has an average crystal width of about 0.3 μm up to about 1.5 μm, e.g., about 0.3 to about 1 μm, or about 0.3 to about 0.5 μm. For example, the thickness of flaky CHA-type zeolite crystals can be less than about 0.05 μm, e.g., about 0.01 to about 0.03 μm, or about 0.02 to about 0.025 μm. The average crystal size can be measured, for example, using microscopy, e.g., scanning electron microscopy (SEM) alone or in combination with energy dispersive X-ray spectroscopy (EDS). In some embodiments, the aspect ratio (ratio of longest dimension to thickness) is greater than about 10, e.g., greater than about 20, or greater than about 30. In some embodiments, the aspect ratio is about 20 to about 40. In some embodiments, the aspect ratio is about 10, about 15, about 20, about 25, about 30, about 35, or about 40.
[0257] By "predominantly flaky" is meant that greater than about 40% of the crystals present in a sample of CHA-type zeolite prepared as disclosed herein have a flaky morphology, e.g., based on average measurements obtained from SEM / EDS. For example, in some embodiments, at least about 50%, at least about 60%, at least about 70%, at least about 80%, at least about 90%, at least about 95%, or at least about 99% of the crystals have a flaky morphology.
[0258] The CHA-type zeolite product having a flake-like morphology can also be characterized by its silica-to-alumina molar ratio (SAR). In one embodiment, the SAR molar ratio of the CHA-type zeolite ranges from 2 to 60. In a particular embodiment, the CHA-type zeolite product has an SAR of about 10 to about 30. In a particular embodiment, the CHA-type zeolite product has an SAR of about 15 to about 25.
[0259] The CHA-type zeolite product having a flake-like morphology can also be characterized by its silica-to-potassium (Si / K) molar ratio. In one embodiment, the CHA-type zeolite has a Si / K molar ratio of less than about 20. In certain embodiments, the CHA-type zeolite product has a Si / K molar ratio of from about 20 to about 10, e.g., from about 20, about 19, about 18, about 17, about 16, or about 15 to about 14, about 13, about 12, about 11, or about 10. In certain embodiments, the CHA-type zeolite product has a Si / K molar ratio of from about 12 to about 17.
[0260] Promoted CHA-type zeolite In some embodiments, the CHA-type zeolites disclosed herein are further treated with a promoter metal to form a metal-promoted (e.g., ion-exchanged) zeolite catalyst. As used herein, the term "promoted" refers to a metal component ("promoter metal") that is intentionally added to the molecular sieve material, as opposed to an inherent impurity in the molecular sieve. Thus, a promoter is intentionally added to improve the activity of the catalyst compared to a catalyst that does not have the intentionally added promoter. The promoter metal actively participates in promoting a chemical reaction; for example, copper participates in the conversion of nitrogen oxides and is therefore often referred to as an active metal. In one or more embodiments, a suitable metal is independently exchanged into the disclosed CHA-type zeolites to promote the selective catalytic reduction of nitrogen oxides in the presence of ammonia.
[0261] In some embodiments, the disclosed zeolites are promoted with a promoter metal selected from the group consisting of alkali metals, alkaline earth metals, Group IIIB, IVB, VB, VIB, VIIB, VIIIB, IB, and IIB transition metals, Group IIIA elements, Group IVA elements, lanthanides, actinides, and combinations thereof. In some embodiments, promoter metals that may be used to prepare the promoted zeolites of the disclosed catalyst compositions include, but are not limited to, copper (Cu), cobalt (Co), nickel (Ni), lanthanum (La), manganese (Mn), iron (Fe), vanadium (V), silver (Ag), cerium (Ce), neodymium (Nd), praseodymium (Pr), titanium (Ti), chromium (Cr), zinc (Zn), tin (Sn), niobium (Nb), molybdenum (Mo), hafnium (Hf), yttrium (Y), tungsten (W), and combinations thereof. In some embodiments, the promoter metal is copper, manganese, iron, or a combination thereof. In some embodiments, the promoter metal is copper, iron, or a combination thereof. For example, copper and / or iron can be ion-exchanged to form Cu-chabazite, Fe-chabazite, or Cu / Fe-chabazite. When copper acetate is used, the copper concentration of the liquid copper solution used in copper ion exchange is, in certain embodiments, in the range of about 0.01 to about 0.4 molar, more specifically, in the range of about 0.05 to about 0.3 molar.
[0262] The promoter metal can be exchanged into the zeolite by a liquid-phase exchange process, in which soluble metal ions exchange with protons or ammonium or sodium ions located within the pores of the zeolite. The exchange can also be carried out by a solid-state process, in which solid particles of the promoter metal oxide or metal salt are mixed with zeolite powder and treated under a specific temperature and gas environment, which may or may not contain steam. The exchange process can also be achieved via an in situ process during slurry preparation, in which fine metal oxide particles are suspended in a zeolite slurry under conditions favorable for solid-liquid interaction. In some embodiments, before exchanging the CHA-type zeolite disclosed herein with the promoter metal, the zeolite is subjected to a H + To obtain the form, NH4 + must be replaced and fired.
[0263] To further promote SCR of nitrogen oxides, in some embodiments, the zeolite can be promoted with two or more metals (e.g., copper in combination with one or more other metals). When two or more metals are included in the promoted zeolitic material, multiple metal precursors (e.g., copper and iron precursors) can be ion-exchanged simultaneously or separately. In certain embodiments, a second metal can be exchanged into a zeolitic material initially promoted with a first metal (e.g., a second metal can be exchanged into a zeolitic material promoted with copper).
[0264] In one or more embodiments, the promoter metal content, calculated as oxide, can independently range from about 0.01 wt. % to about 15 wt. %, from about 0.5 wt. % to about 12 wt. %, or from about 1.0 wt. % to about 10 wt. %, based on the total weight of the corresponding calcined zeolite (including the promoter metal), reported on a volatile-free basis. In some embodiments, the promoter metal content, calculated as oxide, is at least about 0.1 wt. %, based on the total weight of the corresponding calcined zeolite (including the promoter metal), reported on a volatile-free basis. In certain embodiments, the promoter metal of the zeolite comprises Cu, and the Cu content, calculated as CuO, ranges from about 0.1 wt. % to about 20 wt. %, e.g., from about 0.5 wt. % to about 17 wt. %, from about 2 wt. % to about 15 wt. %, or from about 2 wt. % to about 10 wt. %, in each case based on the total weight of the calcined zeolite, reported on a volatile-free basis.
[0265] In some embodiments, zeolites (including promoter metals) can be defined by the ratio of promoter metal to aluminum within the promoted zeolite. For example, in some embodiments, the weight ratio of promoter metal to aluminum ranges from about 0.002 to about 0.5. In particular embodiments, the promoter metal of the zeolite comprises Cu, and the atomic ratio of copper to aluminum in the zeolite is from about 0.1 to about 0.5 (e.g., the Cu / Al ratio is from about 0.1 to about 0.5).
[0266] SCR catalyst composition The present disclosure relates to the reduction of NO from engine exhaust gas, such as from a lean-burn engine, in the presence of a reducing agent. x The present invention provides a selective catalytic reduction (SCR) catalyst composition effective for catalyzing the reduction of toluene, the catalyst composition comprising a promoted CHA-type zeolite as disclosed herein.
[0267] Without wishing to be bound by theory, CHA crystals having a predominantly flake-like morphology may exhibit different behavior during coating, which may prove advantageous from the standpoint of SCR performance. In addition to different coating and packing behavior, the flake-like morphology may allow for more efficient mass transfer of reactants and products across the CHA crystals, thus reducing the likelihood of mass transport limitations in the coated catalyst. Thus, the present disclosure provides a method for reducing NO from engine exhaust gases, such as from lean-burn engines, in the presence of a reducing agent. x The present invention provides a selective catalytic reduction (SCR) catalyst composition effective for catalyzing the reduction of toluene, the catalyst composition comprising a promoted CHA-type zeolite as disclosed herein.
[0268] In some embodiments, the SCR catalyst composition may further include a binder, such as a ZrO binder derived from a suitable precursor, such as zirconyl acetate, or any other suitable zirconium precursor, such as zirconyl nitrate. Zirconyl acetate binders provide a coating that remains uniform and intact after heat aging, for example, when the catalyst is exposed to high temperatures of at least about 600°C, e.g., about 800°C or higher, and high water vapor environments of about 5% or higher. Other potentially suitable binders include, but are not limited to, alumina and silica. Alumina binders include aluminum oxide, aluminum hydroxide, and aluminum oxyhydroxide. Aluminum salts and colloidal forms of alumina may also be used. Silica binders include various forms of SiO, including silicates and colloidal silica. The binder composition may include any combination of zirconia, alumina, and silica. Other exemplary binders include boehmite, gamma-alumina, or delta / theta alumina, and silica sol. When present, binders are typically used in an amount of about 1-5 wt. % of the total washcoat loading. Alternatively, the binder may be zirconia- or silica-based, e.g., zirconium acetate, zirconia sol, or silica sol. When present, alumina binders are typically used in an amount of about 0.05 g / in 3 ~Approx. 1g / in3 is used in amounts of
[0269] NO x Absorbent composition The CHA-type zeolite of the present disclosure can, for example, x It may have utility in certain NOx absorber compositions, such as the absorber (LT-NA). x One relatively new LT-NA useful for low temperature trapping of NO utilizes palladium-exchanged zeolites to trap NO without catalytic pre-oxidation to NO, as described in U.S. Patent Application Publication No. 2017 / 0096922, which is incorporated herein by reference. Thus, in another aspect, nitrogen oxides (NO) in the exhaust gas stream can be trapped. x The present invention provides an LT-NA catalyst composition effective for mitigating CO₂ emissions, the LT-NA catalyst comprising a CHA-type zeolite material disclosed herein promoted with a platinum group metal.
[0270] As used herein, "platinum group metal component" or "PGM component" refers to platinum group metals or their oxides, including platinum (Pt), palladium (Pd), ruthenium (Ru), rhodium (Rh), osmium (Os), iridium (Ir), and mixtures thereof. In some embodiments, the PGM component includes palladium, platinum, rhodium, rhenium, ruthenium, iridium, or a combination thereof. In some embodiments, the PGM component includes palladium, platinum, or a mixture thereof. In other embodiments, the platinum group metal component includes two platinum group metals, for example, in a weight ratio of about 1:10 to about 10:1. For example, in some embodiments, the platinum group metal component includes platinum and palladium. In some embodiments, NO x The absorber composition specifically excludes platinum.
[0271] The concentration of the platinum group metal component can vary, but will typically be from about 0.01% to about 10% by weight, based on the total weight of the impregnated zeolite. In some embodiments, the NOx absorbent composition is substantially free of platinum. As used herein, the term "substantially free of platinum" refers to the absence or presence of NOx. x No additional platinum intentionally added to the absorber composition, and NO x This means that there is less than about 0.01% by weight of platinum metal present in the absorber composition.
[0272] Other catalyst compositions and methods The zeolites of the present disclosure may have utility in catalyzing many other chemical reactions such as olefin formation, including the conversion of alcohols to olefins, hydrocarbon cracking, the formation of methylamines, and the partial oxidation of methane to methanol.
[0273] Accordingly, in another aspect, there is provided a catalyst composition effective for one or more conversions selected from olefin formation, hydrocarbon cracking, removal of alcohols to form olefins, formation of methylamines from methanol and ammonia, and partial oxidation of methane to methanol, the catalyst composition comprising an intergrowth zeolite having a CHA framework structure as disclosed herein.
[0274] Zeolites with a CHA framework have been reported as catalysts for methanol to olefins (see, e.g., Deimund, et al., ACS Catalysis 2016, 6, 542-550; Corma et al., Chemistry-A European Journal 2018; and Nishitoba et al., Industrial & Engineering Chemistry Research 2018, 57, 3914-3922, the disclosures of each of which are incorporated herein by reference). Zeolites with a CHA framework have been reported for partial methane oxidation (PMO) to methanol (see, e.g., Snyder et al., Chemical Reviews 2018, 118, 2718-2768; Li et al., ACS Catalysis 2018, 8, 10119-10130; and Newton et al., Journal of the American Chemical Society 2018, 140, 10090-10093, the disclosures of each of which are incorporated herein by reference).
[0275] In one embodiment, the intergrowth zeolite is H + In other embodiments, the intergrown zeolite is promoted with one or more metals, such as transition metals.
[0276] In one embodiment, a catalyst composition effective for the partial oxidation of methane to methanol is provided, the catalyst comprising an intergrowth zeolite having a CHA framework structure as disclosed herein promoted with copper, iron, or a combination thereof.
[0277] In another aspect, there is provided a method for treating a gas stream comprising one or more of an alcohol, a hydrocarbon, ammonia, or a combination thereof, the method comprising contacting the gas stream with an intergrowth zeolite having a CHA framework structure disclosed herein for a time and at a temperature effective to catalyze one or more reactions selected from oxidation, reduction, elimination, and carbon-carbon bond breaking.
[0278] catalyst article In another embodiment, NO from engine exhaust, such as from a lean-burn engine, in the presence of a reductant. x The present invention provides an SCR article effective for catalyzing the reduction of HCl, the SCR article including a substrate having an inlet end and an outlet end defining an overall length, and an SCR catalyst composition disclosed herein disposed on at least a portion of the substrate.
[0279] Base material In one or more embodiments, the catalyst composition (e.g., an SCR or LT-NA composition) is disposed on a substrate to form a catalytic article. Catalytic articles comprising the substrate are typically used as part of an exhaust gas treatment system (including, but not limited to, articles comprising the SCR or LT-NA compositions disclosed herein). Useful substrates are three-dimensional, having a length, diameter, and volume resembling a cylinder. The shape does not necessarily conform to a cylinder. The length is the axial length defined by the inlet and outlet ends.
[0280] According to one or more embodiments, the substrate for the disclosed compositions can be composed of any material typically used to prepare automotive catalysts, and typically includes a metal or ceramic honeycomb structure. The substrate typically provides a plurality of walls onto which the washcoat composition is applied and adheres, thereby serving as a substrate for the catalyst composition.
[0281] The ceramic substrate may be made from any suitable refractory material, such as cordierite, cordierite-α-alumina, aluminum titanate, silicon titanate, silicon carbide, silicon nitride, zircon mullite, spodumene, alumina-silica-magnesia, zircon silicate, sillimanite, magnesium silicate, zircon, petalite, α-alumina, aluminosilicates, and the like.
[0282] The substrate can also be metallic and include one or more metals or metal alloys. Metal substrates can include any metallic substrate having openings or "punchouts" in the channel walls. Metallic substrates can be used in various shapes, such as pellets, compressed metallic fibers, corrugated sheets, or monolith forms. Specific examples of metallic substrates include heat-resistant base metal alloys, particularly alloys in which iron is a substantial or major component. Such alloys can contain one or more of nickel, chromium, and aluminum, the total of which can advantageously comprise at least about 15% by weight (weight percent) of the alloy, in each case based on the weight of the substrate, e.g., about 10 to about 25% by weight chromium, about 1 to about 8% by weight aluminum, and 0 to about 20% by weight nickel. Examples of metallic substrates include those with straight channels, those with protruding blades along the axial channels to disrupt gas flow and open gas flow communication between channels, and those with holes to enhance gas transport between channels, allowing radial gas transport throughout the blades and monolith.
[0283] Any suitable substrate for the catalytic articles disclosed herein may be used, such as a monolithic substrate of the type having fine, parallel gas passages extending therethrough from an inlet or outlet face of the substrate so that the passages are open to the fluid flow therethrough (a "flow-through substrate"). Another suitable substrate is one of the type having a plurality of fine, substantially parallel gas passages extending along the longitudinal axis of the substrate, typically with each passage blocked at one end of the substrate body and every other passage blocked at the opposite end face (a "wall-flow filter"). Flow-through and wall-flow substrates are also disclosed, for example, in International Application No. 2016 / 070090, the entire contents of which are incorporated herein by reference.
[0284] In some embodiments, the catalytic substrate comprises a honeycomb substrate in the form of a wall-flow filter or a flow-through substrate. In some embodiments, the substrate is a wall-flow filter. In some embodiments, the substrate is a flow-through substrate. Flow-through substrates and wall-flow filters are discussed further herein below.
[0285] Flow-Through Substrate In some embodiments, the substrate is a flow-through substrate (e.g., a monolithic substrate, including a flow-through honeycomb monolithic substrate). Flow-through substrates have fine, parallel gas flow passages extending from the inlet end to the outlet end of the substrate such that the passages are open to fluid flow. The passages, which are essentially straight-line paths from the fluid inlet to the fluid outlet, are defined by walls, and catalytic coatings are disposed on or within the walls such that gas flowing through the passages contacts the catalytic material. The flow passages in flow-through substrates are thin-walled channels and can be of any suitable cross-sectional shape and size, such as trapezoidal, rectangular, square, sinusoidal, hexagonal, elliptical, circular, etc. Flow-through substrates can be ceramic or metallic, as described above.
[0286] The flow-through substrate may be, for example, about 50 in 3 ~About 1200in 3 and a cell density (inlet opening) of about 60 cells per square inch (cpsi) to about 500 cpsi or up to 900 cpsi, e.g., about 200 to 400 cpsi, and a wall thickness of about 50 to about 200 microns or about 400 microns.
[0287] Wall flow filter substrate In some embodiments, the substrate is a wall-flow filter, which generally has a plurality of fine, substantially parallel gas passages extending along the substrate's longitudinal axis. Typically, each passage is blocked at one end of the substrate body, and every other passage is blocked at the opposite end. Such monolithic wall-flow filter substrates may contain up to about 900 or more passages (or "cells") per square inch of cross section, although much smaller numbers may be used. For example, the substrate may have about 7 to 600, more typically about 100 to 400, cells per square inch ("cpsi"). The cells may have rectangular, square, circular, oval, triangular, hexagonal, or other polygonal cross sections. Wall-flow filter substrates may be ceramic or metallic, as described above.
[0288] Referring to FIG. 2, an exemplary wall-flow filter substrate is cylindrical and has a cylindrical outer surface with a diameter D and an axial length L. A cross-sectional view of a monolithic wall-flow filter substrate is shown in FIG. 3a, depicting alternating blocked and open passages (cells). Blocked or blocked ends 100 alternate with open passages 101, with the opposite ends being open and blocked, respectively. The filter has an inlet end 102 and an outlet end 103. Arrows across the porous cell walls 104 represent exhaust gas flow entering the open cell ends, diffusing through the porous cell walls 104, and exiting the open outlet cell ends. The blocked ends 100 impede gas flow and promote diffusion through the cell walls. Each cell wall has an inlet side 104a and an outlet side 104b. The passages are enclosed by the cell walls.
[0289] The wall flow filter article substrate may be, for example, about 50 cm 3 , about 100in 3 , approximately 200 in 3 , about 300in 3 , approximately 400in 3 , approximately 500 in 3 , approximately 600 in 3 , approximately 700 in 3 , approximately 800 in 3, approximately 900in 3 , or about 1000 in 3 From about 1500 in 3 , approximately 2000 in 3 , about 2500in 3 , about 3000in 3 , about 3500in 3 , approximately 4000in 3 , approximately 4500 in 3 , or about 5000 in 3 Wall-flow filter substrates typically have a wall thickness of from about 50 microns to about 2000 microns, for example, from about 50 microns to about 450 microns, or from about 150 microns to about 400 microns.
[0290] The walls of a wall-flow filter are porous and generally have a wall porosity of at least about 40% or at least about 50% and an average pore size of at least about 10 microns before the functional coating is applied. For example, the wall-flow filter article substrate in some embodiments has a porosity of ≥40%, ≥50%, ≥60%, ≥65%, or ≥70%. For example, the wall-flow filter article substrate may have a wall porosity of about 50%, about 60%, about 65%, or about 70% to about 75% and an average pore size of about 10 microns or about 20 microns to about 30 microns or about 40 microns before the catalytic coating is applied. The terms "wall porosity" and "substrate porosity" are interchangeable and mean the same thing. Porosity is the ratio of the void volume (or pore volume) divided by the total volume of the substrate material. Pore size and pore size distribution are typically determined by Hg porosimetry measurements.
[0291] Substrate Coating Process To produce the catalytic articles of the present disclosure, a substrate as described herein is coated with a catalytic composition as disclosed herein (e.g., an SCR or LT-NA catalyst composition). The coating is a "catalytic coating composition" or "catalytic coating." "Catalyst composition" and "catalytic coating composition" are synonymous.
[0292] Generally, a catalyst composition is prepared as described herein and coated onto a substrate. The method can include mixing a catalyst composition generally disclosed herein (or one or more components of the catalyst composition) with a solvent (e.g., water) to form a slurry for coating the catalyst substrate. In addition to the catalyst composition, the slurry can optionally contain various additional components. Typical additional components include, but are not limited to, binders as described herein above, such as additives for controlling the pH and viscosity of the slurry. Additional components can include hydrocarbon (HC) storage components (e.g., zeolites), associative thickeners, and / or surfactants (including anionic, cationic, nonionic, or amphoteric surfactants). The typical pH range of the slurry is about 3 to about 6. Acidic or basic species can be added to the slurry to adjust the pH. For example, in some embodiments, the pH of the slurry is adjusted by the addition of aqueous acetic acid.
[0293] The slurry can be milled to reduce particle size and improve particle mixing and formation of a homogeneous material. Milling can be accomplished in a ball mill, continuous mill, or other similar equipment, and the solids content of the slurry can be, for example, about 20 to 60% by weight, more specifically, about 20 to 40% by weight. In one embodiment, the slurry after milling has a D of about 1 to about 40 microns, preferably 2 to about 20 microns, and more preferably about 4 to about 15 microns. 90 It is characterized by particle size.
[0294] The catalyst composition may typically be applied in the form of one or more washcoats containing the catalyst composition as disclosed herein. The washcoat is formed by preparing a slurry containing a particular solids content (e.g., about 10 to about 60 wt.%) of the catalyst composition (or one or more components of the catalyst composition) in a liquid vehicle, which is then applied to a substrate using any washcoating technique known in the art, dried, and calcined to provide a coating layer. If multiple coatings are applied, the substrate is dried and / or calcined after each washcoat is applied, and / or after a desired number of multiple washcoats are applied. In one or more embodiments, the catalytic material is applied to the substrate as a washcoat.
[0295] After calcination, the catalyst loading achieved by the washcoating technique can be determined by calculating the difference between the coated and uncoated weights of the substrate. As will be apparent to those skilled in the art, the catalyst loading can be modified by changing the rheology of the slurry. Furthermore, the coating / drying / calcining process to produce a washcoat layer can be repeated as necessary to build the coating to a desired loading level or thickness, i.e., more than one washcoat can be applied.
[0296] Coating Composition The catalytic coating can include one or more coating layers, at least one of which includes the catalyst composition or one or more components of the catalyst composition. The catalytic coating can include one or more thin, adherent coating layers disposed on and adhering to at least a portion of a substrate. The overall coating includes the individual "coating layers."
[0297] In some embodiments, the catalyst article may include the use of one or more catalytic layers, as well as combinations of one or more catalytic layers. The catalytic material may be present only on the inlet side, only on the outlet side, on both the inlet and outlet sides of the substrate wall, or the wall itself may be composed entirely or partially of catalytic material. The catalytic coating may be on the substrate wall surface and / or within the pores of the substrate wall, i.e., "in" and / or "on" the substrate wall. Thus, the phrase "a washcoat disposed on a substrate" refers to any surface, e.g., on the wall surface and / or on the pore surface.
[0298] Washcoats can be applied so that the different coating layers are in direct contact with the substrate. Alternatively, one or more "undercoats" may be present, whereby the catalytic coating layer or at least a portion of the coating layer is not in direct contact with the substrate (rather, it is in contact with the undercoat). One or more "overcoats" may be present so that at least a portion of the coating layer is not directly exposed to the gas stream or atmosphere (rather, it is in contact with the overcoat).
[0299] Alternatively, the catalyst composition may be present in a top coating layer that overlies the bottom coating layer. The catalyst composition may be present in both the top and bottom layers. Any one layer may extend the entire axial length of the substrate; for example, the bottom layer may extend the entire axial length of the substrate, and the top layer may also extend the entire axial length of the substrate above the bottom layer. The top and bottom layers may each extend from either the inlet end or the outlet end.
[0300] For example, both the bottom coating layer and the top coating layer can extend from the same substrate edge, with the top layer partially or completely overlaying the bottom layer, with the bottom layer extending a partial or full length of the substrate, and the top layer extending a partial or full length of the substrate. Alternatively, the top layer can overlay a portion of the bottom layer. For example, the bottom layer can extend the full length of the substrate, and the top layer can extend from either the inlet or outlet edge for about 10%, about 20%, about 30%, about 40%, about 50%, about 60%, about 70%, about 80%, or about 90% of the length of the substrate.
[0301] Alternatively, the bottom layer may extend from either the inlet end or the outlet end up to about 10%, about 15%, about 25%, about 30%, about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, about 85%, or about 95% of the length of the substrate, and the top layer may extend from either the inlet end or the outlet end up to about 10%, about 15%, about 25%, about 30%, about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, about 85%, or about 95% of the length of the substrate, with at least a portion of the top layer overlaying the bottom layer. This "overlay" zone can extend, for example, from about 5% to about 80%, e.g., about 5%, about 10%, about 20%, about 30%, about 40%, about 50%, about 60, or about 70%, of the length of the substrate.
[0302] The catalytic coating can advantageously be "zoned" and include zoned catalytic layers, i.e., the catalytic coating contains different compositions across the axial length of the substrate. This may also be described as "laterally zoned." For example, a layer may extend from the inlet end toward the outlet end and may extend over about 10%, about 20%, about 30%, about 40%, about 50%, about 60%, about 70%, about 80%, or about 90% of the substrate length. Another layer may extend from the outlet end toward the inlet end and may extend over about 10%, about 20%, about 30%, about 40%, about 50%, about 60%, about 70%, about 80%, or about 90% of the substrate length. Different coating layers may be adjacent to each other and not overlay each other. Alternatively, different layers may overlap portions of each other to provide a third, "intermediate" zone. The intermediate zone may, for example, extend over about 5% to about 80% of the substrate length, such as about 5%, about 10%, about 20%, about 30%, about 40%, about 50%, about 60%, or about 70% of the substrate length.
[0303] The zones of the present disclosure are defined by the relationship between coating layers. There are several possible zoning configurations for different coating layers. For example, there may be an upstream zone and a downstream zone; an upstream zone, an intermediate zone, and a downstream zone; or four different zones. When two layers are adjacent and do not overlap, there are upstream and downstream zones. When two layers overlap to some extent, there are upstream, downstream, and intermediate zones. For example, when a coating layer extends over the entire length of the substrate and a different coating layer extends a certain length from the exit end and overlays a portion of the first coating layer, there are upstream and downstream zones.
[0304] For example, an SCR catalyst article may include an upstream zone including a first washcoat layer and a downstream zone including a second washcoat layer including a different catalytic material or component, or the upstream zone may include the second washcoat layer and the downstream zone may include the first washcoat layer.
[0305] In some embodiments, the first washcoat is disposed on the catalyst substrate from the inlet end for about 10% to about 50% of its total length, and the second washcoat is disposed on the catalyst substrate from the outlet end for about 50% to about 90% of its total length. In some embodiments, the first washcoat is disposed on the catalyst substrate from the outlet end for about 10% to about 50% of its total length, and the second washcoat is disposed on the catalyst substrate from the inlet end for about 50% to about 90% of its total length.
[0306] Figures 3b, 3c, and 3d illustrate several possible coating layer configurations with two coating layers. Substrate wall 200 is shown, on which coating layers 201 (top coat) and 202 (bottom coat) are disposed. This is a simplified illustration; for porous wall-flow substrates, the pores and coatings attached to the pore walls are not shown, and plugged ends are not shown. In Figure 3b, coating layers 201 and 202 each extend the entire length of the substrate, with top layer 201 overlaying bottom layer 202. The substrate in Figure 3b does not include a zoned coating configuration. Figure 3c illustrates a zoned configuration with coating layer 202 extending approximately 50% of the substrate length from the outlet to form downstream zone 204, and coating layer 201 extending approximately 50% of the substrate length from the inlet to provide upstream zone 203. In Figure 3d, bottom coating layer 202 extends approximately 50% of the substrate length from the outlet, and top coating layer 201 extends more than 50% of the substrate length from the inlet, overlaying a portion of layer 202, providing upstream zone 203, intermediate overlay zone 205, and downstream zone 204. Figures 3b, 3c, and 3d can be useful in illustrating catalyst composition coatings on wall-through or flow-through substrates.
[0307] In some embodiments, the substrate is a honeycomb substrate. In some embodiments, the honeycomb substrate is a flow-through substrate or a wall-flow filter. In certain embodiments, the SCR catalyst composition disclosed herein, when incorporated into the SCR catalyst article disclosed herein, in the presence of a reductant, reduces NO from engine exhaust gas, such as exhaust from a lean-burn engine. x The current product is effective in catalyzing the reduction of NO over a range of temperatures. x In some embodiments, the compound is effective in catalyzing the reduction of NO x Effective reduction of NO is at temperatures above about 150° C. and below about 700° C. In some embodiments, NO x Effective reduction occurs at temperatures between about 200°C and about 600°C.
[0308] Exhaust Gas Treatment Systems In a further aspect, a system for treating an exhaust gas stream from an engine is provided, the system including an SCR article disclosed herein located downstream of and in fluid communication with an engine producing the exhaust gas stream, such as a lean-burn engine. The engine may be, for example, a diesel engine operating under combustion conditions with more air than required for stoichiometric combustion, i.e., lean conditions. In other embodiments, the engine may be a gasoline engine (e.g., a lean-burn gasoline engine) or an engine associated with a stationary power source (e.g., a generator or pumping station). The exhaust gas treatment system generally contains two or more catalytic articles disposed downstream of the engine in fluid communication with the exhaust gas stream. The system may include, for example, a selective catalytic reduction catalyst (SCR) disclosed herein, a diesel oxidation catalyst (DOC), and one or more articles including a reductant injector, a soot filter, an ammonia oxidation catalyst (AMOx), or a lean NOx trap (LNT). An article including a reductant injector is a reduction article. The reduction system may include a reductant injector, a pump, a reservoir, and / or the like. The treatment system may further include a soot filter and / or an ammonia oxidation catalyst. The soot filter may be uncatalyzed or catalyzed (CSF). For example, the treatment system may include, from upstream to downstream, a DOC-containing component, a CSF, a urea injector, an SCR component, and an AMOx-containing component. A lean NOx trap (LNT) may also be included.
[0309] The relative placement of the various catalytic components present within the emissions treatment system can vary. In the present exhaust gas treatment systems and methods, the exhaust gas stream is received into the article or treatment system by entering at an upstream end and exiting at a downstream end. The inlet end of the substrate or article is synonymous with the "upstream" end or "front" end. The outlet end is synonymous with the "downstream" end or "rear" end. The treatment system is generally downstream of and in fluid communication with the internal combustion engine.
[0310] One exemplary emissions treatment system is illustrated in FIG. 4, which depicts a schematic diagram of an emissions treatment system 20. As shown, the emissions treatment system may include multiple catalyst components in series downstream of an engine 22, such as a lean-burn gasoline engine. At least one of the catalyst components will be an SCR catalyst of the present invention as described herein. The catalyst composition of the present invention may be combined with a number of additional catalyst materials and may be located in various positions relative to the additional catalyst materials. While FIG. 4 illustrates five catalyst components 24, 26, 28, 30, and 32 in series, the total number of catalyst components may vary, and five components is merely an example.
[0311] Without limitation, Table 1 presents various exhaust gas treatment system configurations of one or more embodiments. Note that each catalyst is connected to the next catalyst via an exhaust conduit such that the engine is upstream of catalyst A, which is upstream of catalyst B, which is upstream of catalyst C, which is upstream of catalyst D, and which is upstream of catalyst E (if present). References to components A-E in the table may be cross-referenced with the same symbols in FIG. 4.
[0312] The LNT catalysts listed in Table 1 x It can be any catalyst conventionally used as a trap, typically including base metal oxides (such as BaO, MgO, CeO, etc.) and platinum group metals (e.g., Pt and Rh) for catalytic oxidation and reduction of NO. x The adsorbent composition includes:
[0313] The LT-NA catalysts listed in Table 1 produce NO at low temperatures (<250°C). x It can be any catalyst that can adsorb NO (e.g., NO or NO2) and release it into the gas stream at high temperatures (>250°C). xis typically converted to N2 and HO over a downstream SCR or SCRoF catalyst. Typically, the LT-NA catalyst comprises a Pd-promoted zeolite or a Pd-promoted refractory metal oxide. In some embodiments, the LT-NA comprises a promoted CHA-type zeolite having a flake morphology as described herein.
[0314] References to SCR in the tables refer to an SCR catalyst, which may include the SCR catalyst composition of the present invention. References to SCRoF (i.e., SCR over filter) refer to a particulate or soot filter (e.g., a wall-flow filter), which may include the SCR catalyst composition of the present invention. When both an SCR and an SCRoF are present, one or both could include the SCR catalyst of the present invention, or one of the catalysts could include a conventional SCR catalyst (e.g., an SCR catalyst with a conventional metal loading level).
[0315] References to AMOx in the tables refer to an ammonia oxidation catalyst that can be provided downstream of the catalyst of one or more embodiments of the present invention to remove any fugitive ammonia from the exhaust gas treatment system. In certain embodiments, the AMOx catalyst can include a PGM component. In one or more embodiments, the AMOx catalyst can include a bottom coat having a PGM and a top coat having SCR functionality.
[0316] As will be appreciated by those skilled in the art, in the configurations listed in Table 1, any one or more of components A, B, C, D, or E may be disposed on a particulate filter, such as a wall-flow filter, or on a flow-through honeycomb substrate. In one or more embodiments, the engine exhaust system includes one or more catalyst compositions mounted in a location near the engine (direct-coupled location, CC), with an additional catalyst composition in an underbody location (underfloor location, UF). In one or more embodiments, the exhaust gas treatment system may further include a urea injection component. [Table 1]
[0317] How to treat engine exhaust Another aspect of the present invention relates to a method for treating an exhaust gas stream from an engine, such as a lean-burn engine, particularly a lean-burn gasoline or diesel engine. The method can include placing a catalytic article according to one or more embodiments of the present disclosure downstream of the engine and flowing the engine exhaust gas stream over the catalyst. In one or more embodiments, the method further includes placing an additional catalytic component downstream of the engine, as described above. The catalytic compositions, articles, systems, and methods are suitable for treating exhaust gas streams from internal combustion engines, such as gasoline, light-duty diesel, and heavy-duty diesel engines. The catalytic compositions are also suitable for treating emissions from stationary industrial processes, removing harmful or toxic substances from indoor air, or catalyzing chemical reaction processes.
[0318] The articles, systems, and methods of the present invention are suitable for treating exhaust gas streams from mobile exhaust sources such as trucks and automobiles. The articles, systems, and methods of the present invention are also suitable for treating exhaust streams from stationary sources such as power plants.
[0319] It will be readily apparent to those skilled in the relevant art that suitable modifications and adaptations to the compositions, methods, and applications described herein can be made without departing from the scope of any embodiment or aspect thereof. The compositions and methods provided are exemplary and are not intended to limit the scope of the claimed embodiments. All of the various embodiments, aspects, and options disclosed herein can be combined in all variations. The scope of the compositions, formulations, methods, and processes described herein includes all actual or potential combinations of the embodiments, aspects, options, examples, and preferences herein. All patents and publications cited herein are incorporated by reference for their specific teachings, as described, unless other specific statements of incorporation are specifically provided.
[0320] Although the invention herein has been described with reference to particular embodiments, it is to be understood that these embodiments are merely illustrative of the principles and applications of the present invention. It will be apparent to those skilled in the art that various modifications and variations can be made to the disclosed method and apparatus without departing from the spirit and scope of the invention. Therefore, it is intended that the present invention cover modifications and variations that come within the scope of the appended claims and their equivalents. References throughout this specification to "one embodiment," "a particular embodiment," "one or more embodiments," or "an embodiment" mean that a particular feature, structure, material, or characteristic described in connection with an embodiment is included in at least one embodiment of the invention. Thus, the appearances of phrases such as "in one or more embodiments," "in a particular embodiment," "in one embodiment," or "in an embodiment" in various places throughout this specification are not necessarily all referring to the same embodiment of the invention. Furthermore, particular features, structures, materials, or characteristics may be combined in any suitable manner in one or more embodiments. All ranges cited herein are inclusive.
[0321] The present invention will now be described with reference to the following examples. Before describing certain exemplary embodiments of the invention, it is to be understood that this invention is not limited to the details of construction or process steps set forth in the following description. The invention is capable of other embodiments and of being practiced or carried out in various ways.
[0322] experiment I. CHA-type zeolites with controlled Al sites Example 1.Na + and TMAda + Preparation of CHA using (comparison) Comparative CHA-type zeolites were prepared according to the procedures disclosed in U.S. Patent Application Publication No. 2017 / 0107114, which is incorporated herein by reference in its entirety, using aluminum isopropoxide (Al(Oi-Pr)), colloidal silica (AS-40; 40 wt. % SiO), Na as an inorganic structure directing agent, and PEG-40 as a zeolite stabilizer.+ (as NaOH), and trimethyl-1-adamantylammonium hydroxide (TMAda) as an organic structure directing agent (OSDA). + After crystallization, each material was filtered, washed with deionized water, and calcined at 540 °C in air.
[0323] Figures 5a-5d show the results for Si / Al = 15 and Na+ / TMAda. + The X-ray diffraction patterns of CHA-type zeolites synthesized using a Na ratio of 0 or 1 are shown. + and TMAda + Typical syntheses in the presence of TMAda showed that the crystallized zeolites had a significant fraction of paired aluminum atoms present in the structure. These samples showed that using Al(Oi-Pr)3 as the Al precursor yielded CHA-type zeolites containing nearly 40% of the Al atoms in paired arrangements, nearly twice the number that would be expected for a statistically random distribution of Al in a CHA-type zeolite of this composition (Si / Al=15). + CHA-type zeolites crystallized in a synthesis medium containing only TMAda but in the presence of Al(Oi-Pr)3. + and did not contain paired Al sites, consistent with previous observations on CHA synthesized using only aluminum hydroxide (Al(OH)3) as the Al source (Figure 6) (Di Iorio, JR; Gounder, R. Chem. Mater. 2016, 28, 2236-2247). 2+ ions were used to determine whether the Al atoms occurred as pairs (during 6MR) or as separated ions (Figure 6). 2+ The fraction of paired Al measured by exchange is shown as a function of the number of paired Al predicted for a random Al distribution according to Lowenstein's law (OH - Al(OH)3 and Na in the medium + / TMAda + = 0–2 (gray squares), Al(Oi-Pr)3 and Na + / TMAda + =1 (black square), F - Na in medium + / TMAda + = 0 (gray circle), and Na + / TMAda + =0 (black circle).
[0324] Therefore, Na in the CHA synthesis medium + In the presence of Al precursor (Al(OH)3 or Al(Oi-Pr)3), Na + / TMAda + = 0, Co / Al < 0.01) or mineralizers (e.g., OH - or F - ), paired Al sites are formed regardless of the cation structure used to promote zeolite crystallization, suggesting that the structure of the cation used to promote zeolite crystallization primarily influences the Al sites. While not wishing to be bound by any particular theory, these results taken together suggest that organic TMAda + Molecular and inorganic alkali cations (e.g., Na + ) stabilizes paired Al sites and leads to the formation of paired Al sites during CHA crystallization. This suggests that the number of paired Al sites in CHA is proportional to the number of TMAda in the crystallized CHA-type zeolite product. + With Na + This is consistent with previous experimental observations that the co-incorporation of
[0325] Example 2.K + and TMAda + CHA preparation using (invention). Regarding the above hypothesis, during CHA synthesis, TMAda + Along with Na as the alkaline SDA cation + Instead of K + Further investigation was carried out by using K +suppresses the formation of certain crystalline phases (e.g., BEA, MFI, etc.) and also promotes the crystallization of low-silica CHA (Si / Al<5) from the FAU precursor in the absence of organic SDA, and promotes the crystallization of Na without the use of high-concentration seeds (approximately 10 wt% SiO2 seeds). + These observations support the idea that K + This suggests that Na may direct crystallization towards the CHA framework, but its role in influencing the Al arrangement is likely unclear. + It gives different results. + K on the Al arrangement in high-silica CHA (Si / Al=15) crystallized in the presence of + The effect of different Na + / TMAda + This was investigated by adapting a previously reported procedure for synthesizing CHA using the ratio (Di Iorio, JR; Gounder, R. Chem. Mater. 2016, 28, 2236-2247, incorporated herein by reference in its entirety), but by substituting KOH for NaOH in the synthesis solution.
[0326] A synthetic molar ratio of 1 SiO2 / 0.033 Al2O3 / X TMAdaOH / 0.5*(0.5-X)K2O / 44 H2O was used for 15 CHA-type zeolite SAR. + TMAda +The ratio of α to β was controlled by varying the value of X between 0 and 0.5. A typical synthesis involved adding the desired amount of aqueous TMAdaOH solution (25 wt%, Sachem) to deionized HO (18.2 MΩ) in a perfluoroalkoxyalkane (PFA) jar and stirring the solution under ambient conditions for 5 minutes, capped. Next, Al(OH) (98 wt%, SPI Pharma) and 5 M potassium hydroxide solution (KOH: 21.9 wt% KOH in deionized water, 98 wt% KOH pellets, Alfa Aesar) were added to the aqueous TMAdaOH solution, and the mixture was stirred under ambient conditions for 15 minutes, capped, to homogenize the contents. Finally, colloidal silica (Ludox HS40, 40 wt%, Sigma Aldrich) was added to the mixture, capped, and stirred under ambient conditions for 2 hours. All synthetic reagents were used without further purification. The synthesis solution was then transferred to a 45 ml Teflon-lined stainless steel autoclave (Parr Instruments) and placed in a forced convection oven (Yamato DKN-402C) at 160 °C and rotated at approximately 40 RPM for 6 days.
[0327] K + / TMAda + Synthesis media containing ≦20 yield CHA-type zeolites with no detectable phase impurities in the X-ray diffraction (XRD) data (Fig. 7a–h), whereas K + / TMAda + If we increase it beyond 20 (K + / TMAda + (up to ∞), MFI was formed. Specifically, Figures 7a-7h show 、 K + / TMAda + (a) 1, (b) 2, (c) 3, (d) 4, (e) 5, (f) 10, (g) 15, and (h) 20. Figures 8a-d provide X-ray diffraction patterns for CHA embodiments synthesized using Al(Oi-Pr)3 at Si / Al = 15 and K + / TMAda +The XRD patterns of zeolites with ratios of 30, 50, 100, and infinity are provided. Figure 8e provides the XRD of MFI-type zeolite for comparison.
[0328] This is because TMAda, which helps induce the CHA phase, + This reflects the role of + alone was unable to crystallize CHA under the synthesis conditions disclosed herein. + When using Na as an alkaline source, + Alkaline / TMAda is an order of magnitude higher than when using + CHA could be crystallized from solutions containing the same ratio (MOR was observed at Na / TMAda > 2). + have highlighted the ability of different alkali cations to function as co-SDAs with K (Lobo, RF; Zones, SI; Davis, ME Journal of Inclusion Phenomena and Molecular Recognition in Chemistry 1995, 21, 47-78). + and suppress the formation of other undesired phases, as previously suggested for the synthesis of IFR-type zeolites from mixtures of benzyl mono- and di-azabicyclo complexes (Muraoka et al., Angewandte Chemie International Edition 2018, 130, 3804-3808). + This seems to reflect the trend.
[0329] K + / TMAda + SEM micrographs (Figures 9a-9h) of CHA zeolites synthesized at <10 K consisted of cubic crystals ranging in size from 4 to 8 μm and had similar compositions (Table 2). Referring to Figures 9a-9h, the results are shown for (a) 1, (b) 2, (c) 3, (d) 4, (e) 5, (f) 10, (g) 15, and (h) 20 K. + / TMAda +SEM micrographs taken at 1300x magnification of CHA synthesized at the ratio K are provided. + / TMAda + The CHA synthesized at >10 consisted of a mixture of two distinct crystalline CHA phases that were significantly differentiated in size and composition (Table 2), including a low-silica, K-rich CHA phase (Si / Al<7, K + / Al>1.5) is K + / TMAda + <10(Si / Al>10, K + The results show that the CHA phase begins to form in parallel with the high-silica CHA phase, which is the major crystalline product from synthesis solutions containing SiO2 / Al<0.70. [Table 2]
[0330] This observation suggests that K + / TMAda + The CHA synthesized at <10 was almost pure high-silica CHA, but + / TMAda + This was consistent with refined X-ray diffraction (XRD) data showing that only 67% of the material synthesized from the solution containing SiO2 was composed of the high-silica CHA phase. Table 3 shows the K determined by powder X-ray diffraction. + / TMAda + The parameters determined for the embodiments with ratios of 2, 10, and 20 are provided. Elemental analysis of these two different CHA phases by EDX reveals that the high silica CHA phase is K + / TMAda + The results showed that the CHA samples synthesized at <10 had similar elemental compositions to other CHA samples (Table 2 and Figure 10). [Table 3]
[0331] K +Almost all CHA-type zeolites synthesized using HCl contained visible defects (Figures 11a and 11b to 18a and 18b), which are likely the formation of large mesopores, and this was due to the absence of alkali (TMAda). + (only) or Na + and TMAda + This was not observed in the CHA synthesized using the mixture of Ar and K. + / TMAda + =2, the CHA synthesized is TMAda + and Na + Different mixtures of (0.19cm 3 g -1 ) and contained no mesopores, as evidenced by the absence of desorption hysteresis (Figure 19).
[0332] K + / TMAda + The CHA synthesized at 15°C had a significantly lower Ar micropore volume (0.06 cm) than expected for CHA. 3 g -1 ) and exhibits H4-type desorption hysteresis (step down at P / P of about 0.4, Figure 20), which indicates that excess cationic charge density (K + This set of data indicates the presence of disordered mesopores, possibly formed by defects introduced from the K phase (Table 3) or from adsorption within the secondary phase. + The role of Na + Unlike the role of TMAda, occlusion during crystallization + This suggests that the Al atoms in the synthesis medium were not replaced by Na (Fig. 21a), which was reflected in the Al arrangement of the crystalline product. + / TMAda + TMAda per CHA cage measured by thermogravimetric analysis (TGA) as a function of the ratio + The number of CHA cages (squares) and the Na retained per CHA cage measured by AAS. +The amount (circles) is shown on the graph.
[0333] Na + and TMAda + The comparative CHA zeolite crystallized from the mixture of + One TMAda per cage, regardless of the amount of + (approximately 20-22 wt. % organic) (Fig. 21a), but K + and TMAda + The zeolite of the present invention crystallized from the mixture of + As the amount of TMAda increases, + The occupancy of TMAda per CHA cage decreased in an orderly fashion (Fig. 21b, Table 2). + Number (squares) and K retained per CHA cage + The amount (circle) of K in synthetic medium + / TMAda + It is shown graphically as a function of the ratio.
[0334] Without wishing to be bound by theory, it is believed that TMAda + and K. + The negative correlation observed between the three K + The cation is a single TMAda + from the CHA cage, and K+ is replaced by approximately two TMAda per unit cell. + This suggests that the K retained in the crystalline CHA product helps stabilize the CHA skeleton to a maximum extent (Fig. 21c). + (square) or Na + TMAda per CHA cage as a function of the amount of (circular) + The dashed line (slope approximately 1 / 3) and the dotted line (slope approximately 0) represent the number of K + (square) and Na + (Circle) is a regression to the dataset.
[0335] The total Al content is K+ Although it increased with increasing content (Table 2), it was due to the presence of excess cationic charges (e.g., (K + +TMAda + ) / Al>1, Table 4) is K + This suggests that the formation of anionic lattice defects was necessary to compensate for the excess extraframework charge in CHA synthesized using cationic ions (Table 4). Table 4 shows the total K per Al. + and TMAda + content, total cationic charge of the crystalline zeolite product ((K + +TMAda + ) / Al), H + / Al ratio, and K + / TMAda + = 1-20. + Proton titration by ion exchange is + / TMAda + It was shown that CHA-type zeolites synthesized at <10 contained almost all Al in framework positions, but + / TMAda + Further increasing the ratio, hydrated NH 4+ The proportion of Al that is inaccessible to cations is high, probably due to the K + / TMAda + reflecting pore blockage or the formation of extraframework Al sites in CHA synthesized at >10 (Table 4). [Table 4]
[0336] Na retained in the crystalline product + As the total amount of Na increases, + Co in CHA synthesized by 2+It has been previously reported that the number of paired Al sites (two Al in 6-MR) quantified by titration increases (Di Iorio, JR; Gounder, R. Chem. Mater. 2016, 28, 2236-2247; et al., ACS Catal. 2017, 7, 6663-6674). In contrast, the K retained after crystallization + The total amount of K in the synthetic medium was not correlated with the number of Al pairs (Table 2). + / TMAda ratio is low (K + / TMAda<2) and K + A small amount of paired Al sites was formed by the absorption of Na. + and TMAda + This was lower than the amount previously reported for CHA synthesized with a mixture of Co / Al (Co / Al = 0.10) (Co / Al = 0.05). + / TMAda + As the ratio increases, the K in the crystallographic product + The ratio of K to TMAda increased in a systematic manner (Fig. 21b). + However, for similar voids in CHA, TMAda + This suggests that the Na+ and Na+ atoms competed with each other, favoring the formation of isolated Al sites. + The behavior of TMAda is significantly different from that of the tetrahydrofuran, which stabilizes the two anionic charges in the paired Al configuration. + Na in the void space not occupied by + These results reflect the preference of the extra-framework cationic SDA to stabilize different Al arrangements during CHA crystallization, and the prevalence of extra-framework Cu. 2+ and H + This is consistent with previous findings that cations preferentially stabilize different Al arrangements within CHA.
[0337] Example 3.Na + and TMAda + Large-scale preparation of CHA zeolite using (comparison). Large-scale synthesis (300 ml reactor volume) was performed using inorganic SDA (as NaOH) and Na+ and TMAda as organic SDA + The synthesis was carried out using a PTFE autoclave. A typical synthesis involved adding the desired amount of sodium hydroxide to deionized water weighed into the PTFE liner of an autoclave. The solution was stirred for 5 minutes. Next, the desired amount of 20 wt% TMAdaOH solution (Sachem) was added, and the mixture was stirred for 5 minutes. An aluminum source (aluminum hydroxide) was added to the mixture and stirred for 30 minutes. Finally, the desired amount of colloidal silica (Ludox AS-40) was added to the mixture and stirred for 60 minutes. The PTFE liner with the mixture was placed in the autoclave, which was then sealed and maintained at 160 °C for 72 hours with stirring at 250 rpm. Table 5 provides the OH / Si ratio, inorganic / organic SDA ratio, Si / Al ratio in the synthesis gel, water / Si ratio, and phases determined by XRD for the products of each experiment. [Table 5]
[0338] Example 4.K + and TMAda + Large-scale preparation of CHA-type zeolite using (invention) Large-scale synthesis (300 ml or 2 L reactors) was performed using inorganic SDA (as KOH) and KOH. + and TMAda as organic SDA +The synthesis was carried out using a PTFE autoclave. A typical synthesis involved adding the desired amount of 45 wt.% potassium hydroxide to deionized water weighed into the PTFE liner of an autoclave. The solution was stirred for 5 minutes. Next, the desired amount of 20 wt.% TMAdaOH solution (Sachem) was added, and the mixture was stirred for 5 minutes. An aluminum source (AH = aluminum hydroxide, AIP = aluminum isopropoxide) was added to the mixture and stirred for 30 minutes. Finally, the desired amount of colloidal silica (Ludox AS-40) was added to the mixture and stirred for 60 minutes. The PTFE liner with the mixture was placed in an autoclave, which was sealed and maintained at 160 °C for 72 hours with stirring at 250 rpm. Table 6 provides the OH / Si ratio, K / TMAda ratio, Si / Al ratio in the synthesis gel, water / Si ratio, and phases determined by XRD for the products of each experiment. [Table 6]
[0339] In general, the results demonstrated that organic and inorganic cations cooperate or compete for occupancy within the void space of chabazite-type zeolite, affecting the framework Al arrangement in the CHA-type zeolite of essentially fixed composition, resulting in, in some embodiments, intergrowths of crystalline phases (mixed domains). In Experiment #3, the proportions of the first and second phases in the product were determined to be approximately 20-30% and 70-80%, respectively. The unit cell volume of these phases was 2353 Å. 3 ~2411Å 3 The range was.
[0340] The results disclosed herein suggest that CHA-type zeolites with similar microscopic arrangements of framework Al atoms can be enhanced by the addition of organic TMAda that alters the dominant SDA-framework interactions, which influences the positioning of Al. + This paper highlights how Na can be prepared from synthetic protocols using different alkali cations. + preferentially occupies the 6-MR void of the CHA and +In the presence of α, paired Al sites are stabilized, and they are occluded within a larger CHA cage, forming a TMAda + This suggests cooperative interactions that stabilize regions of locally higher anionic charge density (i.e., paired Al) than could be stabilized by Al alone.
[0341] K + The cations are TMAda for occupancy in the CHA cage. + compete with and ultimately high K + Concentration (K + / TMAda + >2) TMAda + which results in the substitution of Na + (Na + / TMAda + >2) than is possible in the synthetic medium (K + / TMAda + These observations may reflect the different roles that cationic SDA plays in stabilizing zeolite frameworks containing high anionic charge densities. + The cation is TMAda + Na that does not compete with and causes the formation of paired Al sites + In contrast, TMAda is more likely to occupy the large CHA cage. + These findings provide a methodology to investigate the cooperative and competitive interactions of mixtures of organic and inorganic SDAs during zeolite crystallization, and also offer opportunities to design zeolitic materials with tailored adsorption and catalytic functions.
[0342] Example 5. Cu-exchanged CHA-type zeolite and SCR activity Next, TMAda + and Na as an SDA aid. + or K + The CHA-type zeolite synthesized using a mixture of Cu and NO was exchanged with NH3. xThe catalytic performance of Cu-CHA type zeolite synthesized without alkali or Na-type zeolite was evaluated for selective catalytic reduction (SCR) of ethanol. + / TMAda + =1(comparison), K + / TMAda + =2 and K + / TMAda + = 15 (invention) for Cu-CHA type zeolite synthesized by H before Cu exchange + / Al, Cu / Al after Cu exchange, and H + / Al, standard NH3-SCR ratings (473°K, per Cu), reaction orders for NO, O2, and NH3, and apparent activation energies are provided. [Table 7]
[0343] NO x The turnover rate of SCR (per Cu, 473°K) is approximately equal to the spatial density of nominally site-separated Cu cations (1000 Å 3 The amount of Cu per [Cu(NH3)2] depends on the arrangement of anionic framework Al atoms that anchor such cationic Cu complexes. + This reflects the O2 oxidation process involving the complex, which is electrostatically constrained at anionic framework Al sites with localized mobility, becoming the rate-limiting process at low temperatures. The stability of Cu-CHA zeolites is due to the Cu 2+ and [CuOH] + It also depends on the distribution of complexes, which exchange at paired and isolated Al sites, respectively, due to differences in their resistance to deactivation by sulfur poisoning and hydrothermal aging. + or K + TMAda + The Cu-exchanged CHA-type zeolite synthesized using the zeolite ion exchanger (before hydrothermal aging) showed similar NO xThe SCR evaluation (per Cu, 473°K), apparent reactant order, and activation energy were consistent with those previously reported for Cu-CHA with similar Cu density (Cu per 10 3 Å 3 ;Paolucci et al.,Science 2017,357,898-903).
[0344] Na + or K + / TMAda + Cu-CHA synthesized using <10 deactivated to a similar extent after hydrothermal aging (10 vol% HO, 1073°K, 16 h, Table 7), which indicates similar Al arrangement and total Al incorporation (H + This suggests that the stability of the CHA framework with K / Al > 0.90 is not affected by the synthesis procedure. + / TMAda + Cu-CHA synthesized at 15°C exhibited more severe deactivation after hydrothermal aging, which is probably due to the + / TMAda + This reflects the highly defective nature of CHA-type zeolites prepared at temperatures >10, which are characterized by H + / Al count and low alkaline / TMAda + ratio, or contained micropore volumes that deviated significantly from those of CHA prepared in alkali-free crystallization media.
[0345] These results suggest that organic TMAda + Despite the diverse roles that different alkalis appear to play in directing Al uptake in the presence of cations, this suggests that different alkali cations can be used to synthesize CHA-type zeolites without detectable changes in SCR performance. Finally, without wishing to be bound by theory, the results suggest that the primary role of alkali cations is to modify the interactions between the framework and the occluded structure-directing agent, which influences the location of Al.
[0346] II. Flake-like CHA-type zeolite General procedure for synthesizing CHA-type zeolite Several comparative and inventive CHA-type zeolites (Examples 6-9 below) were synthesized using either aluminum hydroxide (AH) or aluminum isopropoxide (AP) as the aluminum source, colloidal silica (AS-40, 40 wt. % SiO) as the silicon source, sodium hydroxide or potassium hydroxide as the inorganic structure directing agent (SDA), and trimethyl-1-adamantylammonium hydroxide (TMAdaOH) as the organic structure directing agent (OSDA). The procedure was generally carried out according to the disclosure of U.S. Patent Application Publication No. 2017 / 0107114, which is incorporated herein by reference in its entirety, except that the contents of the autoclave were stirred throughout the duration of the crystallization.
[0347] The composition and crystallization conditions of each synthesis gel are provided in Table 8. After crystallization, the synthesis gels were filtered and the zeolite products were washed with deionized water and calcined at 540°C in air. [Table 8]
[0348] Example 6. CHA with truncated cubic crystals (comparison). Following the general procedure, a comparative CHA zeolite was synthesized, the SEM image of which is provided in Figure 22a, showing a truncated cubic morphology.
[0349] Example 7. CHA with cubic aggregates (comparison). Following the general procedure, a comparative CHA zeolite was synthesized, the SEM image of which is provided in Figure 22b, showing cubic crystal morphology aggregated into spherical morphology.
[0350] Example 8. CHA with predominantly flaked morphology (invention). Following the general procedure, the inventive CHA zeolite was synthesized, the SEM image of which is provided in Figure 22c, showing a flake-like morphology with some cubic crystals present.
[0351] Example 9. CHA (invention) with predominantly flake-like morphology. According to the general procedure, the CHA-type zeolite of the invention was synthesized. The SEM image of this CHA-type zeolite is provided in Figure 22d, which shows a flake-like morphology with some cubic crystals present. Both the SEM image (Figure 22d) and TEM image (Figure 23) of a single flake showed that these flakes are not rigid in structure and can bend / fold.
[0352] Figure 24 provides a TEM single-area diffraction pattern (SADP) for the flake zeolite, verifying that the material is crystalline. The d-spacings derived from the rings in this pattern are listed in the inset of Figure 24, and they match, within the experimental error of the technique, the significantly diffracting d-spacings of the CHA-type zeolite structure. The ring corresponding to a d-spacing of 0.94 nm (corresponding to the (100) plane of the CHA crystal structure) appears to be masked by scattering from the beam stop used in the experiment.
[0353] Example 10. X-ray diffraction (XRD) patterns XRD patterns for the materials described in Examples 6-9 are provided in Figures 25a-25d, respectively, and demonstrate the CHA crystalline structure of each material. For the inventive materials of Examples 8 and 9 (Figures 25c and 25d, respectively), the XRD exhibits peak anisotropy, particularly at higher angles (15-40°).
[0354] Example 11. Elemental composition of morphology. Samples of inventive Examples 8 and 9 were analyzed by energy dispersive X-ray spectroscopy (EDS). Specifically, multiple points on the cubic and flake crystals present in each sample were analyzed to provide averaged multi-point relative concentrations of Si, Al, Na, and K. These data are provided in Table 9. [Table 9]
[0355] Example 12. Flake crystal dimensions. The average dimensions of the flake crystals in the samples of Examples 8 and 9 were determined from multiple measurements taken from SEM images at high magnification (20,000x). The flake dimensions were highly variable. Folding, overlapping, and tearing of the flakes made it difficult to obtain accurate measurements. The average dimensions for each sample are provided in Table 10. While these values are estimated and should not be considered limiting, the data generally indicated that the inventive materials had very thin cross sections relative to their length and width, consistent with a flake-like morphology. In both samples, few flakes larger than 1.5 μm in their longer dimension were observed. [Table 10]
[0356] The average flake thickness (Z) measurements were 0.021 □m and 0.025 □m, respectively, for the samples of Examples 8 and 9. It is possible that the flakes are thinner than this data suggests, but the thickness cannot be fully resolved due to orientation, folding, and image resolution.
[0357] Example 13. Cubic vs. Flake Morphology Distribution Estimation of the percentage of flakes in the samples of Examples 8 and 9 was performed by combining compositional information from SEM-EDS on individual crystals (flakes and cubic crystals) with overall composition measurements. These data are provided in Table 11. [Table 11]
[0358] Example 14. SCR Performance SCR articles were prepared using a washcoat containing the composition of Example 9. Prior to testing, the catalytic materials were aged at 800°C for 16 hours in the presence of 10% HO / air. x Conversion (Figure 26) was performed using a temperature gradient of 0.5°C / min from 200°C to 600°C, with 500 ppm NO, 500 ppm NH 3、 10% O 2、 80,000h under quasi-steady-state conditions in a gas mixture of 5% H2O and the remainder N2 -1 The NOx conversion was measured in a laboratory reactor at a gas hourly volumetric space velocity of 1000 kJ / s. The data in Figure 26 show that the material had good NOx conversion over a range of temperatures.
Claims
1. 1. A method for synthesizing a zeolite having a CHA crystalline framework, the method comprising: preparing a mixture of water, an aluminum source, a silica source, a source of organic structure directing agent, and an inorganic structure directing agent to form a synthesis gel, wherein the inorganic structure directing agent is a source of potassium cations; and subjecting the synthesis gel to a crystallization process to crystallize the zeolite having the CHA crystalline framework. the zeolite having the CHA crystalline framework is an intergrowth zeolite comprising a first CHA phase and a second CHA phase; the first CHA phase and the second CHA phase each independently have a unit cell volume of about 2338 Å 3 to 2489 Å 3 ; The method, wherein the unit cell volume of the first CHA phase is different from the unit cell volume of the second CHA phase.
2. 10. The method of claim 1, wherein the source of the potassium cations is potassium hydroxide.
3. To prepare adding the source of the organic structure-directing agent, the source of the inorganic structure-directing agent, and a source of aluminum to the water to form an aluminum-containing aqueous solution; a first mixing step comprising mixing the aqueous solution for a first period of time; a second mixing step comprising adding a source of silicon to the aluminum-containing aqueous solution and mixing for a second time to form an aluminosilicate-containing solution.
4. 4. The method of claim 3, wherein the first and second periods of time are each independently from about 1 second to about 24 hours.
5. 5. The method of claim 3 or 4, wherein the first and second mixing steps are carried out at a temperature of from about 20°C to about 100°C.
6. 6. The method of any one of claims 1 to 5, wherein the crystallization process comprises mixing the synthesis gel at a temperature of about 140°C to about 200°C for a time period of about 24 hours to about 6 days.
7. 7. The method of any one of claims 1 to 6, further comprising filtering the crystals formed during the heating step.
8. The method of any one of claims 1 to 7, wherein the source of the organic structure directing agent is N,N,N-trimethyl-1-adamantylammonium hydroxide (TMada).
9. 9. The method of claim 8, wherein the amount of TMada and the amount of the potassium cation source are such that the molar ratio of potassium cations to N,N,N-trimethyl-1-adamantylammonium cations is in a molar ratio ranging from about 1 to about 20.
10. 10. The method of any one of claims 1 to 9, wherein the source of aluminum is aluminum hydroxide, aluminum nitrate, aluminosilicate, aluminum chloride, aluminum phosphate, or aluminum triisopropoxide.
11. 11. The method of any one of claims 1 to 10, wherein the source of aluminum is aluminum hydroxide or aluminum triisopropoxide.
12. 12. The method of any one of claims 1 to 11, wherein the source of aluminium is aluminium hydroxide.
13. 13. The method of any one of claims 1 to 12, wherein the source of silicon is colloidal silica, a silicon alkoxide compound, fumed silica, amorphous silica, or an aluminosilicate.
14. 14. The method of any one of claims 1 to 13, wherein the source of silicon is colloidal silica.
15. 15. The method according to any one of claims 1 to 14, wherein the synthesis gel has an OH / Si ratio of from about 0.1 to about 0.
5.
16. The CHA-type zeolite has a controlled aluminum distribution, and the controlled aluminum distribution is represented by the formula (Al—O(—Si—O) x -Al), wherein: x=1 or 2 and the anionic framework Al centers are in a paired arrangement; or 16. The method of any one of claims 1 to 15, wherein x > 3 and the anionic framework Al centres are in a discrete arrangement.
17. 17. The method of any one of claims 1 to 16, wherein the silica-to-alumina ratio (SAR) of the synthesis gel is selected to provide a CHA-type zeolite having a SAR of from about 2 to about 60.
18. 17. The method of any one of claims 1 to 16, wherein the silica-to-alumina ratio (SAR) of the synthesis gel is selected to provide a CHA-type zeolite having a SAR of from about 6 to about 20.
19. The ratio of the silicon source to the aluminum source to the TMAd to the potassium cation source to the water is determined according to the formula: 1 SiO 2 / 0.033 Al 2 O 3 / X TMAdaOH / 0.5*(0.5-X)K 2 O / 44 H 2 represented by O, 19. The method according to any one of claims 8 to 18, wherein the value of X is from 0.01 to 0.
25.
20. the first CHA phase and the second CHA phase each independently have a silica-to-alumina ratio (SAR) of from about 4 to about 100; 20. The method of any one of claims 1 to 19, wherein the SAR of the first CHA phase is different from the SAR of the second CHA phase.
21. 21. The method of claim 20, wherein the first CHA phase comprises a higher SAR than the second CHA phase.
22. 22. The method of claim 20 or 21, wherein the SAR of the first CHA phase is from about 10 to about 40 and the SAR of the second CHA phase is from about 6 to about 8.
23. 22. The method of claim 21, wherein the SAR of the first CHA phase is from about 10 to about 20.
24. 22. The method of claim 21, wherein the SAR of the first CHA phase is from about 10 to about 15.
25. the first CHA phase represents from about 5% to about 95% of the intergrowth zeolite; the first CHA phase has a potassium cation to aluminum ratio greater than 0.5; 25. The method of any one of claims 1 to 24, wherein the second CHA phase has a potassium cation to aluminum ratio of less than about 0.
5.
26. 26. The method of any one of claims 1 to 25, wherein the first CHA phase, the second CHA phase, or both, comprise a silicoaluminophosphate (SAPO) composition.
27. 27. The method of claim 26, wherein the SAPO composition is SAPO-34 or SAPO-44.
28. 28. The method of any one of claims 1 to 27, wherein the intergrown zeolite crystal size is from about 0.1 to about 15 μm.
29. An intergrowth zeolite having a CHA crystalline framework, the CHA crystalline framework comprises a first CHA phase and a second CHA phase; The first CHA phase and the second CHA phase each independently have a thickness of about 2338 Å 3 ~2489Å 3 and having a unit cell volume of An intergrowth zeolite, wherein the unit cell volume of the first CHA phase is different from the unit cell volume of the second CHA phase.
30. the first CHA phase and the second CHA phase each independently have a silica-to-alumina ratio (SAR) of from about 4 to about 100; 30. The intergrowth zeolite of claim 29, wherein the SAR of the first CHA phase is different from the SAR of the second CHA phase.
31. 31. The intergrowth zeolite of claim 30, wherein the first CHA phase comprises a higher SAR than the second CHA phase.
32. 32. The intergrowth zeolite of claim 31, wherein the SAR of the first CHA phase is from about 10 to about 40, and the SAR of the second CHA phase is from about 6 to about 8.
33. 32. The intergrowth zeolite of claim 31, wherein the SAR of the first CHA phase is from about 10 to about 20.
34. 32. The intergrowth zeolite of claim 31, wherein the SAR of the first CHA phase is from about 10 to about 15.
35. the first CHA phase represents from about 5% to about 95% of the intergrowth zeolite; the first CHA phase has a potassium cation to aluminum ratio greater than 0.5; 35. The intergrowth zeolite of any one of claims 29 to 34, wherein the second CHA phase has a potassium cation to aluminum ratio of less than about 0.
5.
36. 36. The intergrowth zeolite of any one of claims 29 to 35, wherein the first CHA phase, the second CHA phase, or both comprise a silicoaluminophosphate (SAPO) composition.
37. 37. The intergrowth zeolite of claim 36, wherein the SAPO composition is SAPO-34 or SAPO-44.
38. 38. The intergrown zeolite according to any one of claims 29 to 37, wherein the intergrown zeolite crystal size is from about 0.1 to about 15 μm.
39. 39. The intergrowth zeolite of any one of claims 29 to 38, wherein the fraction of aluminum atoms in crystal lattice framework positions of the CHA crystalline framework in the isolated configuration is in the range of from about 0.90 to about 1.
00.
40. 40. The intergrowth zeolite of claim 39, wherein the fraction of the aluminum atoms in crystal lattice framework positions of the CHA crystalline framework in a separated configuration is from about 0.95 to about 1.
00.
41. Nitrogen oxides (NO x 41. A selective catalytic reduction (SCR) catalyst effective for the mitigation of CO₂ emissions, said SCR catalyst comprising the intergrown zeolite material of any one of claims 29 to 40 promoted with a promoter metal.
42. 42. The SCR catalyst of claim 41, wherein the promoter metal is present in an amount of about 1.0 wt. % to about 10 wt. %, calculated as metal oxide, based on the total weight of the SCR catalyst.
43. 43. The SCR catalyst of claim 42, wherein the promoter metal is present in an amount of about 4 to about 6 weight percent.
44. 44. The SCR catalyst of any one of claims 41 to 43, wherein the promoter metal is selected from iron, copper, and combinations thereof.
45. 45. A selective catalytic reduction (SCR) catalyst article effective for reducing nitrogen oxides (NOx) from engine exhaust gases, the SCR catalyst article comprising a substrate having the selective catalytic reduction (SCR) catalyst of any one of claims 41 to 44 disposed on at least a portion of the substrate.
46. 46. The SCR catalyst article of claim 45, wherein the substrate is a honeycomb substrate.
47. 47. The SCR catalyst article of claim 46, wherein the honeycomb substrate is a flow-through substrate or a wall-flow filter.
48. 1. An exhaust gas treatment system comprising: an engine generating an exhaust gas stream; An exhaust gas treatment system comprising: an SCR catalyst article according to any one of claims 45 to 47 positioned downstream of the engine and in fluid communication with the exhaust gas flow.
49. Nitrogen oxides (NO x 41. A low temperature NOx adsorption (LT-NA) catalyst effective for the abatement of NOx adsorption, said LT-NA catalyst comprising the intergrown zeolite material of any one of claims 29 to 40 promoted with a platinum group metal. x Adsorption (LT-NA) catalyst.
50. 41. A catalyst composition effective for one or more conversions selected from olefin formation, hydrocarbon cracking, removal of alcohols to form olefins, formation of methylamines from methanol and ammonia, and partial oxidation of methane to methanol, said catalyst composition comprising the intergrown zeolite material of any one of claims 29 to 40.
51. 1. A zeolitic material having a CHA crystalline framework, wherein the crystals of the zeolitic material have a predominantly flaky morphology as determined by measuring average crystal size using scanning electron microscopy (SEM) at 4800x magnification, wherein the flaky morphology is such that the average length and width of the crystals are between 0.3 and 1.5 μm and the average thickness is less than 0.050 μm.
52. 52. The zeolitic material of claim 51, wherein at least about 40% of the crystals have a flaky morphology as determined by scanning electron microscopy / energy dispersive X-ray spectroscopy (SEM / EDS).
53. 53. The zeolitic material of claim 51 or 52, wherein at least about 70% by weight of the crystals have a flaked morphology.
54. 52. The zeolitic material of claim 51, wherein the average thickness is less than about 0.025 μm.
55. 52. The zeolitic material of claim 51 , wherein the crystal aspect ratio is greater than about 20.
56. 52. The zeolitic material of claim 51, wherein the crystallites have an aspect ratio of from about 20 to about 40.
57. 57. The zeolitic material of any one of claims 51 to 56, wherein the zeolitic material has a silica to alumina molar ratio (SAR) of from about 2 to about 60.
58. 58. The zeolitic material of claim 57, wherein the SAR is from about 10 to about 30.
59. 59. The zeolitic material of any one of claims 51 to 58, wherein the zeolitic material has a silica to potassium molar ratio of less than about 20.
60. 60. The zeolitic material of claim 59, wherein the silica to potassium molar ratio is from about 12 to about 17.
61. A method according to any one of claims 1 to 28, wherein the crystals of the zeolite material have a predominantly flake-like morphology as determined by measuring the average crystal size using scanning electron microscopy (SEM) at 4800x magnification, the flake-like morphology being such that the average length and width of the crystals are between 0.3 and 1.5 μm and the average thickness is less than 0.050 μm.
62. 7. The method of claim 6, wherein the temperature of the crystallization process is from about 160°C to about 180°C.
63. 29. The method of any one of claims 1 to 28, wherein the organic structure directing agent is selected from the group consisting of N,N,N-trimethyl-1-adamantylammonium hydroxide (TMadaOH), trimethylcyclohexylammonium hydroxide, tetraethylammonium hydroxide, benzyltrimethylammonium hydroxide, 1,1,3,5-tetramethylpiperidinium hydroxide, choline hydroxide, N,N-dimethylpiperidinium hydroxide, trimethyl-2-ammonium exo-norbornane, and N-methyl-3-quinuclidinol.
64. 64. The method of claim 63, wherein the organic structure directing agent is TMAdaOH.
65. 65. The method of claim 63 or 64, wherein the inorganic structure directing agent is potassium hydroxide.
66. 66. The method of claim 65, wherein the amount of TMAdaOH and the amount of potassium cations present in the synthesis gel are such that the molar ratio of potassium cations to TMAdaOH is about 10 or greater.
67. 67. The method of claim 66, wherein the molar ratio of potassium cations to TMAdaOH is from about 15 to about 50.
68. 68. The method of any one of claims 64 to 67, wherein the amount of TMAdaOH and the amount of silicon source present in the synthesis gel are such that the molar ratio of TMAdaOH to silicon atoms is less than about 0.
05.
69. 69. The method of claim 68, wherein the molar ratio of TMAdaOH to silicon atoms is from about 0.05 to about 0.
01.
70. 10. The method of any one of claims 1 to 9, wherein the source of aluminum is a zeolite or aluminum isopropoxide.
71. 17. The method of any one of claims 1 to 16, wherein the silica-to-alumina ratio (SAR) of the synthesis gel is selected to provide a zeolite having a SAR of from about 10 to about 30.
72. 72. A zeolitic material having a CHA crystalline framework and a predominantly flaky morphology as determined by scanning electron microscopy / energy dispersive X-ray spectroscopy (SEM / EDS), prepared by the method of any one of claims 61 to 71.
73. Nitrogen oxides (NO x 73. A selective catalytic reduction (SCR) catalyst effective for the mitigation of CO₂ from CO₂, said SCR catalyst comprising the zeolitic material of any one of claims 51 to 60 or claim 72 promoted with a promoter metal.
74. 74. The SCR catalyst of claim 73, wherein the promoter metal is present in an amount of about 1.0 wt % to about 10 wt %, calculated as promoter metal oxide, based on the total weight of the SCR catalyst.
75. 75. The SCR catalyst of claim 74, wherein the promoter metal is present in an amount of about 4 to about 6 weight percent.
76. The SCR catalyst of any one of claims 73 to 75, wherein the promoter metal is a transition metal.
77. 77. The SCR catalyst of any one of claims 73 to 76, wherein the promoter metal is selected from iron, copper, manganese, and combinations thereof.
78. 78. The SCR catalyst of any one of claims 73 to 77, wherein the promoter metal is selected from iron, copper, and combinations thereof.
Citation Information
Patent Citations
Method for producing aluminosilicate
JP2011102209A
A method for the incorporation of aluminum into high silica zeolites prepared in fluoride media
JP2018534230A
Methods of synthesizing chabazite zeolites with controlled aluminum distribution and structures made therefrom
US20170107114A1
CHA aluminosilicate and production method therefor, and exhaust gas purification catalyst, exhaust gas purification apparatus and exhaust gas purification method using same
WO2018221194A1